Polyethylene laminate for sustainable packaging
Patent Information
- Application Number
- CN202280089691.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-11-23
- Filing Date
- 2022-11-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-11-22
AI Technical Summary
该公开文本中没有公开关于SIT、光学性能和机械性能的详细信息,也没有公开关于印刷膜和层压结构的详细信息
Smart Images

Figure BDA0004955895530000331 
Figure BDA0004955895530000371 
Figure BDA0004955895530000381
Abstract
Description
Technical Field
[0001] This invention relates to a polyethylene laminate comprising a printed film and a sealing film. Furthermore, this invention relates to an article comprising the polyethylene laminate, and to the use of the polyethylene laminate in packaging applications. The invention also relates to a sealing film and its use in packaging applications. Background Technology
[0002] Laminated films are widely used in packaging applications. Conventional flexible packaging laminates include various polymer types, such as polyester (e.g., PET) as printing films, polyamide or oriented polypropylene (e.g., BOPP), and polyethylene (PE) as sealing films. Laminated products are typically used in the packaging industry to match the multifunctional needs of different films: the sealing film possesses sufficient toughness-related properties to ensure packaging integrity without deformation or breakage; and the base film possesses stiffness and barrier-related properties to ensure extended shelf life of packaged goods and their subsequent handling and processing, particularly in packaging operations on forming, filling, and sealing (FFS) machines. In addition to excellent sealing performance, sealing films require a balance of impact strength (e.g., dart impact) and mechanical properties (e.g., stiffness, tensile strength) as well as good aesthetic properties (e.g., gloss and transparency). A base film is laminated with a polyethylene sealing film to provide excellent stiffness, heat resistance, optical, and barrier properties.
[0003] Recently, there has been a growing trend towards providing "pure" polyethylene solutions, which involve laminating a polyethylene sealing film onto a substrate also made of polyethylene. Based on a single resin category, these laminates can be easily recycled using conventional methods, improving sustainability, and production costs can be reduced by using cheaper polyethylene polymers. However, the insufficient stiffness and poor heat resistance of the polyethylene substrate may be insufficient to maintain the high packaging speeds on Vertical Form Fill Seal (VFFS) production lines, and cannot withstand the high temperatures of the top sealing clamps, making it difficult to replace traditional substrates with polyethylene substrates. The application of "pure" polyethylene solutions in various FFS machines and different end uses is challenging due to their generally poor stiffness, heat resistance, and barrier properties. Producing a full PE laminate with the required properties to facilitate smooth operation on high-speed VFFS packaging machines, where higher heat resistance is crucial to avoiding film adhesion problems on the sealing clamps, presents a significant challenge. Therefore, although “pure” polyethylene laminates are known, there is still a need to further improve the performance of such laminates, especially when the substrate is produced as a non-oriented PE film.
[0004] WO 2018 / 187438 describes a laminated structure for packaging comprising a sealing film and a layered printed film with a thickness of 15 to 30 micrometers. The intermediate layer of the printed film comprises at least 90 wt.% high-density polyethylene (HDPE) having a density of 0.950 g / cm³. 3 Up to 0.965 g / cm 3 The density and melt index (I2) range from 0.1 g / 10 min to 20 g / 10 min, and both the inner and outer layers contain linear low-density polyethylene (LLDPE) with a density of 0.925 g / cm³. 3 Up to 0.965 g / cm 3 The density. This public document does not disclose detailed information regarding SIT, optical properties, or mechanical properties, nor does it disclose detailed information regarding the printed film and lamination structure. Summary of the Invention
[0005] Therefore, one object of the present invention is to provide a polyethylene laminate, preferably a polyethylene laminate produced by conventional non-directional blown or cast film, which has good or even improved heat resistance and mechanical properties, and thus exhibits excellent performance in high-speed VFFS operation, while also exhibiting excellent sealing performance.
[0006] Another object of the present invention is to provide a polyethylene laminate with good barrier properties, preferably a polyethylene laminate that does not use additional barrier coating (e.g., metallization) steps, which are necessary for the intended use of the laminate in packaging applications, where moisture barrier is particularly important.
[0007] Another object of the present invention is to provide a polyethylene laminate that also meets the aesthetic requirements of films in packaging applications and has good optical properties (e.g., gloss and haze).
[0008] Finally, another object of the present invention is to provide a polyethylene laminate comprising a printed film having the required properties (mechanical and heat resistance) for high-speed printing operation and subsequent use on a packaging line.
[0009] By achieving a combination of these objectives, the present invention provides a polyethylene laminate comprising an inner surface and an outer surface, and said laminate comprises the following:
[0010] a) A printed film comprising an outer layer E, a core layer F, and an inner layer G, wherein the inner layer G forms the outer surface of the laminated film, and wherein the inner layer G is composed of an inner layer G composition comprising component AG, wherein component AG is an ethylene copolymer having a content of 920 kg / m³. 3Up to 935kg / m 3 The density and melt flow rate, determined according to ISO 1133, ranged from 0.5 g / 10 min to 2.0 g / 10 min; and
[0011] b) A sealing film comprising an outer layer A, a core layer B and an inner layer C, wherein the inner layer C forms the inner surface of the laminate, and wherein the inner layer C is composed of an inner layer C composition comprising at least one ethylene polymer.
[0012] Wherein, the outer layer A of the sealing film is laminated to the outer layer E of the printed film, and the sealing initiation temperature (SIT) of the outer surface of the laminated film at 5N is at least 10°C higher than the sealing initiation temperature of the inner surface of the laminated film at 5N, wherein the sealing initiation temperature is determined according to ASTM F2029 and ASTM F88.
[0013] The present invention is based on the discovery that such a polyethylene laminate can be provided by a combination of a printed film and a sealing film, wherein the inner layer of the printed film contains a specifically selected ethylene polymer, and the heat resistance of the outer layer of the laminate is specifically adjusted.
[0014] The above-mentioned objective is achieved by combining the inner layers of the printed film and the sealing film in the polyethylene laminate of the present invention.
[0015] The difference in sealing initiation temperature between the two outer surfaces of the laminated film is at least 10°C, and it has very good mechanical properties, which allows the laminated film to be operated on a VFFS production line at a packaging speed of 50 bags / minute to 80 bags / minute without any jaw-sticking issue at the sealing strip, while achieving excellent sealing performance.
[0016] Excellent barrier properties are achieved in the laminated film without the use of any barrier coating or metallization, which is why the laminated film can be used in most packaging applications without any recyclability issues, where moisture barrier is of particular importance.
[0017] While improving the heat resistance of polyethylene films while maintaining good optical properties is quite challenging, laminated films also possess relatively high gloss and low haze. Therefore, the polyethylene laminated film according to the invention combines all the properties required for laminated films used in packaging applications.
[0018] Furthermore, the printed film of the laminated film can be easily printed on a high-speed printing press.
[0019] In this invention, the polyethylene laminate comprises a sealing film and a printed film, or is composed of a sealing film and a printed film.
[0020] Printing film
[0021] structure
[0022] The term "printed film" refers to a film containing a layer that can be used in printing operations (such as high-speed printing processes). This film can be a non-printed film or a printed film.
[0023] The printed film according to the present invention comprises or is composed of multiple layers, and the multiple layers are at least an outer layer E, a core layer F, and an inner layer G. The core layer F is located between the outer layers, i.e., the outer layer E and the inner layer G. Preferably, the outer layer E of the printed film is a printable layer or a printable layer, i.e., printing can be performed on the outer layer E of the printed film, preferably after surface treatment (corona treatment).
[0024] The printed film also functions as a substrate (film) and contributes to the mechanical and / or optical properties of the laminate. Therefore, in this disclosure, the terms "printed film" and "substrate film" or "substrate" are used synonymously. When the inner layer G is laminated onto the sealing film, it forms the outer surface of the laminate.
[0025] In one embodiment, the printed film comprises an outer layer E, a core layer F, and an inner layer G. In another embodiment, the printed film includes one or more additional intermediate layers (or subsurface layers) Y.
[0026] In one particular embodiment, the printed film further includes one or more intermediate layers Y between the core layer F and the inner layer G, and between the core layer F and the outer layer E, for example in a five-layer film structure E / Y1 / F / Y2 / G or a seven-layer film structure E / Y1 / Y1 / F / Y2 / Y2 / G. Preferably, the printed film comprises up to nine layers, more preferably up to seven layers.
[0027] If present, the one or more intermediate layers Y preferably contain or are composed of components similar to those of their adjacent layers, which could therefore be components of the core layer F, or components of the adjacent inner layer G or the adjacent outer layer E.
[0028] Preferably, the printed film has a thickness of 15 μm to 40 μm, more preferably 20 μm to 38 μm, and most preferably 22 μm to 35 μm.
[0029] Preferably, the core layer F has a thickness of 30% to 80% of the total printed film thickness, more preferably 35% to 75%, and most preferably 40% to 70%.
[0030] The outer layer E and / or the inner layer G preferably each have a thickness of 10% to 35% of the total film thickness, more preferably 15% to 30%, for example, 25%. In the five-layer film structure E / Y1 / F / Y2 / G, the inner layer G and / or the outer layer E preferably each have a thickness of 5% to 25% of the total printed film thickness, more preferably 7.5% to 20%.
[0031] Preferably, the printed film is a "polyethylene film," i.e., a film comprising at least one type of ethylene polymer, or a film composed of at least one type of ethylene polymer, which may be a homopolymer or copolymer of ethylene. Preferably, based on the total weight of the polyethylene film, the polyethylene film contains at least 90 wt.%, more preferably at least 95 wt.%, and most preferably at least 98 wt.% of ethylene polymer. Preferably, based on the total weight of the polyethylene film, the polyethylene film contains 90 wt.% to 100 wt.%, more preferably 95 wt.% to 100 wt.%, and most preferably 98 wt.% to 100 wt.% of ethylene polymer. Most preferably, the polyethylene film consists of only one or more ethylene polymers. Preferably, the ethylene polymer comprises an ethylene homopolymer and / or a copolymer of ethylene with propylene and / or any α-olefin having 4 to 10 carbon atoms, or the ethylene polymer consists of an ethylene homopolymer and / or a copolymer of ethylene with propylene and / or any α-olefin having 4 to 10 carbon atoms. Preferably, the polyethylene film does not contain non-polyolefin polymers, more preferably not non-polyethylene polymers. Particularly preferably, the polyethylene film does not contain polyester or polyamide polymers. The use of polyethylene film enables a fully recyclable and sustainable packaging structure.
[0032] Printed films can typically be supplied as oriented or non-oriented films. Oriented films are those that are "stretched" after production. Oriented films are typically stretched by more than 300% in the machine direction (MD) and / or transverse direction (MD), preferably by more than 500% or more. Films stretched in the machine direction are generally referred to as "MDO" films. Films stretched in both directions are referred to as "bidirectional oriented polyethylene" ("BOPE") films. Non-oriented films are blown or cast films that are not intentionally stretched (preferably by more than 200%) after film production by any appropriate means (i.e., subsequent heating and / or use of rollers during film production).
[0033] Preferably, the printed film is a non-oriented film. Preferably, the printed film is produced on a standard blown film and / or cast film production line using a standard film machine system (take-off rollers and winding machine), without the use of any stretching unit.
[0034] As understood within the scope of this disclosure, the printed film used to prepare the layers and the corresponding layer compositions thereof may also contain additives, such as stabilizers, processing aids, and / or pigments. Examples of such additives include antioxidants, UV stabilizers, acid scavengers, nucleating agents, anti-caking agents, smoothing agents, and polymer processing agents (PPA). These additives may be present in the same or different amounts in some layers of the film or in only one layer. The additives may be added to the individual layer compositions during the preparation of the composition, or they may already be contained in any polymer used to prepare the individual layer compositions.
[0035] Typically, each additive may be present in amounts from 0 ppm to 5000 ppm, based on the total weight of the layer compositions used to prepare the membrane layers. These additives are generally available from various suppliers and are contained in the composition as a single additive or a mixture of two or more additives. Based on the total weight of the layer compositions used to prepare the membrane layers, such compositions may typically be present in amounts from 0 wt.% to 5 wt.% in one or more layer compositions.
[0036] Generally, within the meaning of this disclosure, unless otherwise stated, percentage (%) should be understood as weight percentage (wt.%).
[0037] Composition
[0038] Each of the printed film layers is made of a composition comprising at least one polymer component (e.g., polyethylene). If the composition comprises more than one polymer component, it is a mixture of these components. Additional compounds (e.g., additives such as polymer processing aids, anti-caking agents, or anti-slip agents) may be present in the composition.
[0039] Inner G
[0040] The inner layer G is composed of an inner layer G composition containing components that particularly contribute to the heat resistance and optical properties of the membrane. Furthermore, this membrane also imparts mechanical properties.
[0041] When the inner layer G is laminated onto the sealing film, it forms the outer surface of the laminate. Good optical properties are important for this layer because the printed film used in laminates is typically reverse-printed onto the outer layer.
[0042] Selecting one or more ethylene polymers for the inner layer enables the production of printable films, which is ideal for high-speed printing operations, especially for printing speeds exceeding 200 meters per minute.
[0043] Component AG
[0044] The inner layer G of the printed film is composed of an inner layer G composition containing component AG, which is an ethylene copolymer with a content of 920 kg / m³. 3 Up to 935kg / m 3 The density and melt flow rate (MFR2) of the material were determined according to ISO 1133, ranging from 0.5 g / 10 min to 2.0 g / 10 min.
[0045] Typically, ethylene polymers can be unimodal or multimodal, such as bimodal. The "peak state" of a polymer refers to the structure of its molecular weight distribution, that is, the graphical appearance of the relationship between the number of molecules and the molecular weight. If the curve shows a single maximum value, the polymer is called "unimodal," while if the curve shows a very wide maximum value or two or more maximum values and the polymer consists of two or more components, the polymer is called "bimodal," "multimodal," etc. For example, if the polymer is produced in a continuous, multi-stage process using reactors connected in series and different conditions in each reactor, the polymer components produced in each reactor will each have their own molecular weight distribution and weight-average molecular weight. When recording the molecular weight distribution curves of such a polymer, the individual curves from these components are superimposed onto the overall molecular weight distribution curve of the resulting polymer product, typically producing a curve with two or more distinct maximum values.
[0046] In the production of unimodal ethylene polymers, the ethylene polymers are produced in a reactor under specific conditions regarding monomer composition, hydrogen pressure, temperature, and pressure. As comonomers, other olefins with up to 12 carbon atoms are typically used in the copolymerization of ethylene, such as α-olefins with 3 to 12 carbon atoms, like propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, and 1-decene.
[0047] For example, in the production of bimodal ethylene polymers, a first ethylene polymer is produced in a first reactor under specific conditions regarding monomer composition, hydrogen pressure, temperature, and pressure. After polymerization in the first reactor, a reaction mixture including the produced polymer is fed into a second reactor for further polymerization under different conditions. Typically, the first reactor produces a first polymer with a high melt flow rate (low molecular weight) and with appropriate or minimal amounts of added comonomer, or no such comonomer at all, while the second reactor produces a second polymer with a low melt flow rate (high molecular weight) and with a larger amount of added comonomer. The resulting final product consists of a homogeneous mixture of polymers from both reactors, whose different molecular weight distribution curves together form a molecular weight distribution curve with a broad maximum or two maximums; that is, the final product is a bimodal polymer mixture.
[0048] Preferably, the component AG is a multimodal ethylene copolymer, more preferably a bimodal ethylene copolymer, and even more preferably a copolymer of ethylene and at least two different C4 to C12 α-olefin monomers, i.e., a terpolymer.
[0049] Preferably, the multimodal terpolymer comprises a multimodal polymer of ethylene and at least two different comonomers, or is composed of a multimodal polymer of ethylene and at least two different comonomers, wherein the comonomers are selected from α-olefins having 4 to 10 carbon atoms, and the multimodal polymer has an MFR of 13 to 30. 21 / MFR2 is greater than and MWD is 6 or smaller.
[0050] For example, such multimodal ethylene terpolymers are disclosed in WO 2016 / 083208. For the definition of these ethylene terpolymers (e.g., the “peak” of the polymer) and methods of production, see WO 2016 / 083208. Furthermore, all embodiments and preferred embodiments of such ethylene terpolymers (having the desired density) described in 2016 / 083208 are also preferred embodiments of the multimodal ethylene terpolymers of component AG in this invention, whether explicitly described herein or not.
[0051] The multimodal ethylene terpolymer preferably has an MFR2 in the range of 0.5 g / 10 min to 2.5 g / 10 min, and particularly preferably 1.0 g / 10 min to 1.8 g / 10 min. Preferably, the multimodal ethylene terpolymer has an MFR2 of 922 kg / m³. 3 Up to 933 kg / m 3 More preferably 923 kg / m 3 Up to 930kg / m 3 The density of the multimodal ethylene terpolymer preferably has an MFR of 13 to 30, more preferably 15 to 25. 21 / MFR2 ratio.
[0052] The at least two α-olefin comonomers having 4 to 10 carbon atoms in the multimodal ethylene terpolymer are preferably 1-butene and 1-hexene. Preferably, the total amount of comonomers present in the multimodal ethylene terpolymer is 0.5 mol% to 10 mol%, more preferably 1.0 mol% to 8 mol%, more preferably 1.0 mol% to 5 mol%, and even more preferably 1.1 mol% to 4.0 mol%.
[0053] The preferred bimodal terpolymer is a multimodal ethylene terpolymer that preferably comprises an ethylene polymer component (A1) and an ethylene polymer component (B1), or is composed of an ethylene polymer component (A1) and an ethylene polymer component (B1), wherein the ethylene polymer component (A1) has a higher MFR2 than the ethylene polymer component (B1).
[0054] More preferably, the ethylene polymer component (A1) has an MFR2 of 1 g / 10 min to 50 g / 10 min, preferably 1 g / 10 min to 40 g / 10 min, more preferably 1 g / 10 min to 30 g / 10 min, more preferably 2 g / 10 min to 20 g / 10 min, more preferably 2 g / 10 min to 15 g / 10 min, and even more preferably 2 g / 10 min to 10 g / 10 min.
[0055] The ratio of the MFR2 of the ethylene polymer component (A1) to the MFR2 of the ethylene polymer component (B1) is 2 to 50, preferably 5 to 40, more preferably 10 to 30, even more preferably 10 to 25, and even more preferably 11 to 25.
[0056] Preferably, the ethylene polymer component (A1) comprises a comonomer different from that of the ethylene polymer component (B1). Preferably, the ethylene polymer component (A1) has a lower amount (mol%) of comonomer than the ethylene polymer component (B1). More preferably, the ratio of [the amount (mol%) of α-olefin comonomers having 4 to 10 carbon atoms present in the ethylene polymer component (A1)] to [the amount (mol%) of at least two α-olefin comonomers having 4 to 10 carbon atoms in the final multimodal polymer of ethylene] is 0.2 to 0.6, preferably 0.25 to 0.5.
[0057] Preferably, the α-olefin comonomer having 4 to 10 carbon atoms in the ethylene polymer component (A1) is 1-butene, and the α-olefin comonomer having 4 to 10 carbon atoms in the ethylene polymer component (B1) is 1-hexene. Particularly preferred is that the bimodal terpolymer is prepared in a two-stage or multi-stage polymerization process, wherein the lower α-olefin comonomer (e.g., 1-butene) is introduced via slurry polymerization in a circulating reactor, and wherein the higher α-olefin comonomer (1-hexene) is introduced via gas-phase polymerization in a gas-phase reactor.
[0058] Preferably, the ethylene polymer component (A1) has a density different from that of the ethylene polymer component (B1), and more preferably, it has a higher density than that of the ethylene polymer component (B1). The density of the ethylene polymer component (A1) is preferably 925 kg / m³. 3 Up to 950kg / m 3 More preferably 930 kg / m 3 Up to 945kg / m 3 .
[0059] Preferably, based on the total amount of ethylene polymer (100 wt.%), the multimodal ethylene terpolymer contains 30 wt.% to 70 wt.%, preferably 40 wt.% to 60 wt.%, more preferably 35 wt.% to 50 wt.%, even more preferably 40 wt.% to 50 wt.%, of an ethylene polymer component (A1), and 70 wt.% to 30 wt.%, preferably 60 wt.% to 40 wt.%, more preferably 65 wt.% to 50 wt.%, even more preferably 60 wt.% to 50 wt.%, of an ethylene polymer component (B1).
[0060] Most preferably, the multimodal ethylene terpolymer is composed of ethylene polymer components (A1) and (B1) as the sole polymer components. Accordingly, the ratio between ethylene polymer components (A1) and (B1) is (30 to 70):(70 to 30), preferably (40 to 60):(60 to 40), more preferably (35 to 50):(65 to 50), and even more preferably (40 to 50):(60 to 50).
[0061] In a particularly preferred embodiment, the multimodal terpolymer is a bimodal terpolymer, i.e., comprising low molecular weight and high molecular weight components, and having an MFR2 of 1.0 g / 10 min to 1.8 g / 10 min, and / or an MFR5 of higher than 2.8 g / 10 min to 4.5 g / 10 min, and / or an MFR5 of 20 g / 10 min to 36 g / 10 min. 21 and / or higher than 925 kg / m 3 Up to 929kg / m 3 The density, and / or molecular weight distribution of 3.0 to 5.0 (M w / M n ), and / or 15 kg / mol to 25 kg / mol of M n And / or M from 70 kg / mol to 125 kg / mol w and / or 15 to 25 MFR 21 / MFR2 ratio (FRR) 21 / 2 ), and / or 6 to 9 MFR 21 / MFR5 ratio (FRR) 21 / 5 All molecular weight parameters were determined using standard GPC methods in standard calibration, as described in further detail below.
[0062] As an AG component, resins such as Anteo produced by Borealis or Borouge can be used. TM FK2715.
[0063] Preferably, based on the total weight of the inner layer G composition, the component AG is present in the inner layer G composition in an amount of 40 wt.% to 80 wt.%, more preferably 50 wt.% to 75 wt.%, and most preferably 55 wt.% to 70 wt.%.
[0064] In addition to component AG, the inner layer G composition may also contain other components different from component AG.
[0065] Components BG1 and BG2
[0066] The inner layer G composition may also contain components BG1 and / or BG2.
[0067] Preferably, component BG1 is a linear low-density ethylene polymer (LLDPE) with a density of 915 kg / m³. 3 Up to 930kg / m 3 The density and melt flow rate (MFR2) of the material were determined according to ISO 1133, from 0.05 g / 10 min to 1.0 g / 10 min.
[0068] Such LLDPEs are well known in the art and are typically produced in polymerization processes using catalysts. The LLDPE of component BG1 is preferably a multimodal LLDPE, more preferably a bimodal LLDPE. For example, such a multimodal LLDPE and its production are described in WO 2004 / 000933 A1, see pages 9 to 12 of that document.
[0069] The LLDPE of component BG1 preferably has a density of 920 kg / m³. 3 Up to 928kg / m 3 More preferably 920kg / m 3 Up to 925kg / m 3 The density.
[0070] Preferably, the LLDPE of component BG1 is an ethylene copolymer. The comonomer can be an α-olefin having 4 to 12 carbon atoms, such as 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, or 1-decene. More preferably, the LLDPE is a copolymer of ethylene with 1-butene or 1-hexene, and most preferably a copolymer of ethylene with 1-butene.
[0071] Preferably, the total amount of comonomers present in the LLDPE of component BG1 is 2.0 mol% to 6.0 mol%, more preferably 2.5 mol% to 5.5 mol%, and most preferably 3.0 mol% to 5.2 mol%.
[0072] Preferably, the LLDPE of component BG1 has an MFR2 content of 0.1 g / 10 min to 0.5 g / 10 min, more preferably 0.15 g / 10 min to 0.4 g / 10 min, and most preferably 0.20 g / 10 min to 0.30 g / 10 min.
[0073] The component BG1 preferably has a lower density and / or a lower melt flow rate (MFR2) than component AG.
[0074] In a particularly preferred embodiment, the LLDPE of component BG1 has an MFR2 of 0.2 g / 10 min to 0.3 g / 10 min, and / or an MFR5 of 0.80 g / 10 min to 1.2 g / 10 min, and / or an MFR5 of 18 g / 10 min to 26 g / 10 min. 21 and / or 920kg / m 3 Up to 925kg / m 3 The density, and / or molecular weight distribution (MWD) of 10 to 24, and / or Mn of 10 kg / mol to 15 kg / mol n And / or M of 150 kg / mol to 250 kg / mol w and / or MFR of 80 to 110 21 / MFR2 ratio (FRR) 21 / 2 ), and / or MFR 18 to 26 21 / MFR5 ratio (FRR) 21 / 5 All molecular weight parameters were determined using standard GPC methods in standard calibration, as described in further detail below.
[0075] As the LLDPE component of BG1, resins such as Borstar FB2230 or FB2235 produced by Borealis or Borouge can be used.
[0076] Preferably, component BG2 is a high-density polyethylene polymer (HDPE) with a density of 950 kg / m³. 3 Up to 970kg / m 3 The density and melt flow rate (MFR2) of the material were determined according to ISO 1133, ranging from 0.2 g / 10 min to 2.0 g / 10 min.
[0077] This type of HDPE is well known in the art and is typically produced in polymerization processes using catalysts.
[0078] The HPDE of component BG2 is preferably multi-peaked HDPE, and more preferably bi-peaked HPDE.
[0079] HDPE of component BG2 preferably has a strength of 955 kg / m³.3 Up to 968kg / m 3 More preferably 958 kg / m 3 Up to 965kg / m 3 The density. For example, this type of multimodal HDPE and its production are described in WO 2020 / 109289, see pages 19 to 28 of that document.
[0080] Preferably, the HPDE is a copolymer, and the ethylene copolymer is a copolymer comprising an ethylene monomer and one or more comonomers. The comonomer can be an α-olefin having 4 to 12 carbon atoms, such as 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, or 1-decene. More preferably, the HDPE is a copolymer of ethylene with 1-butene, 1-hexene, or 1-octene, and most preferably a copolymer of ethylene with 1-butene.
[0081] Preferably, the total amount of comonomers present in the HDPE is 0.0 mol% to 0.40 mol%, more preferably 0.01 mol% to 0.30 mol%, and most preferably 0.02 mol% to 0.20 mol%.
[0082] Preferably, the HDPE of component BG2 has an MFR2 content of 0.25 g / 10 min to 1.8 g / 10 min, more preferably 0.3 g / 10 min to 1.5 g / 10 min, even more preferably 0.4 g / 10 min to 1 g / 10 min, and most preferably 0.5 g / 10 min to 0.9 g / 10 min.
[0083] In a particularly preferred embodiment, the HDPE of component BG2 has an MFR2 of 0.5 g / 10 min to 0.9 g / 10 min, and / or an MFR5 of 2.0 g / 10 min to 3.5 g / 10 min, and / or an MFR5 of 30 g / 10 min to 50 g / 10 min. 21 and / or 958 kg / m 3 Up to 965kg / m 3 The density, and / or molecular weight distribution (MWD) of 10 to 15, and / or Mn of 7 kg / mol to 12 kg / mol n And / or M from 100 kg / mol to 165 kg / mol w and / or 50 to 75 MFR 21 / MFR2 ratio (FRR) 21 / 2 ), and / or 10 to 25 MFR 21 / MFR5 ratio (FRR) 21 / 5 All molecular weight parameters were determined using standard GPC methods in standard calibration, as described in further detail below.
[0084] HDPE as component BG2 can be made from resins such as Borstar FB5600 produced by Borouge.
[0085] Preferably, based on the total weight of the inner layer G composition, the components BG1 and / or BG2 are present in the inner layer G composition in an amount of 15 wt.% to 45 wt.%, more preferably in an amount of 20 wt.% to 40 wt.%.
[0086] Component CG
[0087] The inner layer G composition may further comprise component CG. Preferably, the component CG is a low-density ethylene polymer (LDPE), more preferably having a density of 918 kg / m³. 3 Up to 98kg / m 3 LDPE with a density and melt flow rate (MFR2) of 1.5 g / 10 min to 2.5 g / 10 min (as determined according to ISO 1133).
[0088] This type of LDPE is well known in the art and is typically produced in high-pressure processes carried out in tubular reactors or autoclaves.
[0089] For example, LDPE and its production are described in WO 2017 / 055174, see page 9, line 29 to page 12, line 6.
[0090] The preferred LDPE of component CG has a density of 918 kg / m³. 3 Up to 928kg / m 3 More preferably 919 kg / m 3 Up to 927kg / m 3 And the optimal value is 920kg / m 3 Up to 925kg / m 3 The density.
[0091] Preferably, the LDPE of component CG has an MFR2 of 1.6 g / 10 min to 2.4 g / 10 min.
[0092] In a particularly preferred embodiment, the LDPE of component CG has an MFR2 of 1.6 g / 10 min to 2.4 g / 10 min and / or 920 kg / m³. 3 Up to 925kg / m 3 The density, and / or a MWD of 5.5 to 9, and / or a M of 12 kg / mol to 18 kg / mol n And / or M from 80 kg / mol to 130 kg / mol wAll molecular weight parameters were determined by GPC viscosity method in standard calibration, as described in further detail below.
[0093] LDPE used as a component of CG can be resin FT6230 or FT6236 produced by companies such as Borealis or Borouge.
[0094] Preferably, based on the total weight of the inner layer G composition, the component CG is present in the inner layer G composition in an amount of 5 wt.% to 15 wt.%, more preferably in an amount of 7 wt.% to 13 wt.%.
[0095] In one embodiment, the inner layer G composition comprises any of the components AG and BG1 in the above embodiments and optional CG, or is composed of any of the components AG and BG1 in the above embodiments and optional CG.
[0096] In another embodiment, the inner layer G composition comprises any of the components AG and BG2 in the above embodiments and optional CG, or is composed of any of the components AG and BG2 in the above embodiments and optional CG.
[0097] In another embodiment, the inner layer G composition comprises, or is composed of, any of the components AG, BG1, and BG2 in the above embodiments and optional CG.
[0098] In a preferred embodiment, based on the total weight of the inner layer G composition, the inner layer G composition comprises, or is composed of, the following components: 50 wt.% to 75 wt.% of component AG, 25 wt.% to 40 wt.% of any one of component BG1 or BG2, and optionally 0 wt.% to 15 wt.% of component CG.
[0099] Typically, component AG is responsible for the relatively high seal initiation temperature and good optical properties of the printed film. Components BG1 and BG2 further contribute to the high seal initiation temperature without affecting the optical properties of the printed film.
[0100] Core F
[0101] The core layer F of the printed film is composed of a core layer F composition containing components that particularly contribute to the film extrusion process and the film stiffness required for further printing operations (especially high-speed printing operations).
[0102] Component AF
[0103] The core layer F composition may include component AF. Preferably, component AF is a high-density polyethylene polymer (HDPE), preferably having a density of 950 kg / m³. 3 Up to 970kg / m 3 The high-density ethylene polymer with a density and a melt flow rate (MFR2) in the range of 0.2 g / 10 min to 2.0 g / 10 min (as determined according to ISO 1133), as described for component BG2 of the inner layer G composition.
[0104] All embodiments described for component BG2 are embodiments of component AF. Component AF can be independently selected from any of these embodiments, and the selected embodiments can be the same or different for AF and BG2.
[0105] Preferably, based on the total weight of the core layer F composition, the component AF is present in the core layer F composition in an amount of up to 90 wt.%, more preferably from 50 wt.% to 90 wt.%, even more preferably from 60 wt.% to 88 wt.%, and most preferably from 70 wt.% to 87 wt.%.
[0106] The component AF imparts high rigidity to the printed film.
[0107] Component BF
[0108] The core layer F composition may include component BF. Preferably, component BF is an ethylene copolymer, preferably having a content of 920 kg / m³. 3 Up to 935kg / m 3 An ethylene copolymer with a density and a melt flow rate (MFR2) of 0.5 g / 10 min to 2.0 g / 10 min (as determined according to ISO 1133), as described for component AG of the inner layer G composition.
[0109] All embodiments described for component AG are embodiments of component BF. Component BF can be independently selected from any of these embodiments, and the selected embodiments may be the same or different for BF and AG.
[0110] Preferably, based on the total weight of the core layer F composition, the component BF is present in the core layer F composition in an amount of 5 wt.% to 40 wt.%, more preferably in an amount of 10 wt.% to 35 wt.%.
[0111] In one embodiment, the core layer F is composed of a core layer F composition comprising, or consisting of, the components AF and BF, wherein the components AF and BF are selected from any of the embodiments described above.
[0112] In a preferred embodiment, based on the total weight of the core layer F composition, component AF is present in the core layer F composition in an amount of 50 wt.% to 90 wt.%, more preferably 70 wt.% to 87 wt.%, and component BF is present in the core layer F composition in an amount of 10 wt.% to 50 wt.%, more preferably 13 wt.% to 30 wt.%.
[0113] Outer layer E
[0114] The outer layer E of the printed film is composed of an outer layer E composition containing components that particularly contribute to the film's heat resistance, mechanical properties, and optical properties. The outer layer E is preferably a printable or printable layer of the film. In a laminated film, the outer layer E may be disposed between the core layer F and the outer layer A of the sealing film.
[0115] Component AE
[0116] The outer layer E composition may include component AE. Preferably, component AE is an ethylene copolymer, more preferably having a content of 920 kg / m³. 3 Up to 935kg / m 3 An ethylene copolymer with a density and a melt flow rate (MFR2) of 0.5 g / 10 min to 2.0 g / 10 min (as determined according to ISO 1133), as described for component AG of the inner layer G composition.
[0117] All embodiments described for component AG are embodiments of component AE. Component AE can be independently selected from any of these embodiments, and the selected embodiments may be the same or different for AE and AG.
[0118] In one embodiment, the components AE and AG, as well as the optional BF, are the same.
[0119] Preferably, based on the total weight of the outer layer E composition, the component AE is present in the outer layer E composition in an amount of 40 wt.% to 80 wt.%, more preferably 50 wt.% to 75 wt.%, and most preferably 55 wt.% to 70 wt.%.
[0120] Component BE
[0121] The outer layer E composition may include component BE. Preferably, component BE is a linear low-density ethylene polymer (LLDPE), more preferably having a density of 915 kg / m³. 3 Up to 930kg / m 3A linear low-density ethylene polymer with a density of 0.05 g / 10 min to 1.0 g / 10 min (MFR2) (determined according to ISO 1133), as described for component BG1 of the inner layer G composition.
[0122] All embodiments described for component BG1 are embodiments of component BE. Component BE can be independently selected from any of these embodiments, and the selected embodiments can be the same or different for BE and BG1.
[0123] Preferably, based on the total weight of the outer layer E composition, the component BE is present in the outer layer E composition in an amount of 15 wt.% to 40 wt.%, more preferably in an amount of 20 wt.% to 40 wt.%.
[0124] Component CE
[0125] The outer layer E composition may include component CE. Preferably, component CE is a low-density ethylene polymer (LDPE), preferably having a density of 918 kg / m³. 3 Up to 928kg / m 3 The low-density ethylene polymer with a density and a melt flow rate (MFR2) of 1.5 g / 10 min to 2.5 g / 10 min (as determined according to ISO 1133), as described for component CG of the inner layer G composition.
[0126] All embodiments described for component CG are embodiments of component CE. Component CE can be independently selected from any of these embodiments, and the selected embodiments may be the same or different for CE and CG.
[0127] Preferably, based on the total weight of the outer layer E composition, the component CE is present in the outer layer E composition in an amount of 5 wt.% to 15 wt.%, more preferably in an amount of 7 wt.% to 13 wt.%.
[0128] In one embodiment, the outer layer E composition comprises, or is composed of, any of the components AE and BE from the above embodiments and optionally CE.
[0129] In one embodiment, the outer layer E composition comprises the same polymer components (e.g., AG, BG1, and optional CG) as the inner layer G composition, or is composed of the same polymer components as the inner layer G composition.
[0130] In a preferred embodiment, based on the total weight of the outer layer E composition, the outer layer E composition comprises, or is composed of, the following components: component AE in an amount of 50 wt.% to 75 wt.%, component BE in an amount of 25 wt.% to 40 wt.%, and optional component CE in an amount of 0 wt.% to 15 wt.%.
[0131] performance
[0132] The printed film is characterized by high stiffness (e.g., tensile modulus of 500 MPa to 1000 MPa), higher heat resistance (e.g., SIT of 110°C to 120°C), and good optical properties (e.g., haze and gloss). These are achieved in particular by using component AG in the printed film. Furthermore, components BG1 and / or BG2 contribute to improved performance, especially in improving stiffness and / or SIT without sacrificing the optical properties (e.g., haze and gloss) of the printed film.
[0133] sealing film
[0134] structure
[0135] The term "sealing film" refers to a film containing a sealing layer that facilitates bonding with another film, layer, or article.
[0136] The sealing film according to the present invention comprises, or is composed of, multiple layers, including at least an outer layer A, a core layer B, and an inner layer C. The core layer B is located between the outer layers, i.e., between the outer layer A and the inner layer C. Preferably, the inner layer C is a sealing layer. When the inner layer C is laminated onto the printed film, it forms the inner surface of the laminated film.
[0137] In one embodiment, the sealing membrane comprises an outer layer A, a core layer B, and an inner layer C. In another embodiment, the sealing membrane includes one or more additional intermediate (or subsurface) layers X.
[0138] In one particular embodiment, the sealing membrane further comprises a core layer B and an inner layer C, as well as one or more intermediate layers X between the core layer B and the outer layer A, for example, in a five-layer membrane structure A / X1 / B / X2 / C or a seven-layer membrane structure A / X1 / X1 / B / X2 / X2 / C. Preferably, the sealing membrane comprises up to nine layers, more preferably up to seven layers.
[0139] If present, the one or more intermediate layers X preferably comprise a composition similar to that of their adjacent layers, or are composed of a composition similar to that of their adjacent layers, and thus can be any one of the composition of the core layer B or the composition of the adjacent inner layer C or the adjacent outer layer A.
[0140] Preferably, the sealing layer has a thickness of 35 μm to 120 μm, more preferably 40 μm to 110 μm, and most preferably 40 μm to 100 μm.
[0141] In the sealing film, the core layer B preferably has a thickness of 30% to 80% of the total sealing film thickness, more preferably 35% to 75%, and most preferably 40% to 70%.
[0142] The outer layer A and / or the inner layer C preferably each have a thickness of 10% to 35%, more preferably 15% to 30%, for example 25% of the total sealing film thickness. In the five-layer film structure A / X1 / B / X2 / C, the inner layer C and / or the outer layer A preferably each have a thickness of 5% to 20% of the total sealing film thickness, more preferably 7.5% to 15%.
[0143] Preferably, the sealing film is a "polyethylene film" as defined above for printing films.
[0144] The sealing film used for layer preparation and the corresponding layer composition thereof may contain additives of similar types and amounts as described in printed films.
[0145] Preferably, the sealing film is a non-oriented film, with orientation as defined above in relation to the printed film.
[0146] Composition
[0147] Each of the sealing membrane layers is composed of a composition comprising at least one polymer component (e.g., polyethylene). If the composition contains more than one polymer component, it is a mixture of these components. Additional compounds (e.g., additives such as polymer processing aids, anti-caking agents, or lubricants) may be present in the composition.
[0148] Inner layer C
[0149] The inner layer C is composed of an inner layer C composition containing components that particularly contribute to the thermal sealing and optical properties of the film. The inner layer C composition includes at least one ethylene polymer. When laminated onto a printed film, the inner layer C forms the inner surface of the laminated film. The inner layer C of the sealing film is preferably a sealing layer.
[0150] Component AC
[0151] The inner layer C of the sealing membrane is composed of an inner layer C composition containing component AC, which is a linear low-density ethylene polymer (LLDPE) with a density of 915 kg / m³. 3 Up to 925kg / m 3The density and melt flow rate (MFR2) of the material were determined according to ISO 1133, ranging from 0.5 g / 10 min to 2.0 g / 10 min.
[0152] The density of component AC is lower than that of component AG, preferably by at least 3 kg / m³. 3 More preferably, at least 5 kg / m 3 .
[0153] This type of LLDPE is well known in the art and is produced in polymerization processes using catalysts.
[0154] Preferably, component AC is a multimodal ethylene copolymer, more preferably a bimodal ethylene copolymer, and even more preferably a copolymer of ethylene and at least two different C4 to C12 α-olefin monomers, i.e., a terpolymer.
[0155] Preferably, the ethylene copolymer has an MFR of 13 to 30. 21 / MFR2 ratio and MWD of 6 or less.
[0156] Preferably, the ethylene copolymer comprises a multimodal polymer of ethylene and one or more comonomers, or is composed of a multimodal polymer of ethylene and one or more comonomers, wherein the comonomers are selected from α-olefins having 4 to 10 carbon atoms, and the multimodal polymer has an MFR of 13 to 30. 21 / MFR2 ratio and MWD of 6 or less.
[0157] For example, such a multimodal ethylene copolymer is disclosed in WO 2016 / 083208.
[0158] The multimodal ethylene copolymer preferably has an MFR2 content of 0.6 g / 10 min to 2.0 g / 10 min, and particularly preferably 1.2 g / 10 min to 1.8 g / 10 min.
[0159] Preferably, the multimodal ethylene copolymer has a content of 910 kg / m³. 3 Up to 925kg / m 3 More preferably 913 kg / m 3 Up to 922kg / m 3 And 915kg / m³ is particularly preferred. 3 Up to 920kg / m 3 The density.
[0160] The multimodal ethylene copolymer preferably has an MFR of 13 to 30, more preferably 15 to 25. 21 / MFR2 ratio.
[0161] The multimodal ethylene copolymer preferably has a MWD of 6 or less, and typically greater than 1, more preferably 3 to 5.
[0162] The α-olefin comonomer having 4-10 carbon atoms in the multi-peak ethylene copolymer is preferably 1-butene and / or 1-hexene.
[0163] Preferably, the total amount of comonomers present in the multimodal ethylene copolymer is 0.5 mol% to 10 mol%, more preferably 1 mol% to 8 mol%, more preferably 1 mol% to 5 mol%, even more preferably 1.5 mol% to 5 mol%, and most preferably 2.5 mol% to 4 mol%.
[0164] In a preferred embodiment, the multimodal ethylene copolymer is a bimodal copolymer, i.e., it comprises low molecular weight and high molecular weight components and has an MFR2 of 1.2 g / 10 min to 1.8 g / 10 min, and / or an MFR5 of higher than 3.0 g / 10 min to 5.0 g / 10 min, and / or an MFR5 of 20 g / 10 min to 40 g / 10 min. 21 and / or 916 kg / m 3 Up to 920kg / m 3 The density, and / or molecular weight distribution (MWD) of 3 to 5, and / or Mn of 15 kg / mol to 25 kg / mol n And / or M from 80 kg / mol to 115 kg / mol w and / or 15 to 25 MFR 21 / MFR2 ratio (FRR) 21 / 2 ), and / or 6 to 9 MFR 21 / MFR5 ratio (FRR) 21 / 5 ).
[0165] In a further preferred embodiment, the ethylene copolymer of component AC comprises or is composed of ethylene terpolymers, more preferably multimodal ethylene terpolymers (II).
[0166] Preferably, the multimodal ethylene terpolymer (II) is an ethylene terpolymer with a content of 910 kg / m³. 3 Up to 925kg / m 3 The density and MFR2 from 0.5 g / 10 min to 2.0 g / 10 min.
[0167] The multimodal ethylene terpolymer (II) preferably comprises a multimodal polymer containing ethylene and at least two different comonomers, or is composed of a multimodal polymer containing ethylene and at least two different comonomers selected from α-olefins having 4 to 10 carbon atoms, and the multimodal ethylene terpolymer (II) has an MFR of 13 to 30. 21 / MFR2 and 5 or smaller MWD.
[0168] For example, such a multimodal ethylene terpolymer is disclosed in WO 2016 / 083208. For the definition of these ethylene terpolymers (e.g., the “peak state” of the polymer) and methods of production, see WO 2016 / 083208. Furthermore, the ethylene terpolymer described in WO 2016 / 083208 (having a peak state of 910 kg / m³) 3 Up to 925kg / m 3 All embodiments and preferred embodiments of the multimodal ethylene terpolymer (II) of this disclosure, whether or not explicitly described herein, are also preferred embodiments of the multimodal ethylene terpolymer (II).
[0169] The multimodal ethylene terpolymer (II) preferably has an MFR2 content of 0.6 g / 10 min to 2.0 g / 10 min, and particularly preferably 1.2 g / 10 min to 1.8 g / 10 min.
[0170] Preferably, the multimodal ethylene terpolymer (II) has a content of 910 kg / m³. 3 Up to 925kg / m 3 More preferably 913 kg / m 3 Up to 922kg / m 3 And 915kg / m³ is particularly preferred. 3 Up to 920kg / m 3 The density.
[0171] The multimodal ethylene terpolymer (II) preferably has an MFR of 13 to 30, more preferably 15 to 25. 21 / MFR2 ratio.
[0172] The multimodal ethylene terpolymer (II) preferably comprises at least two α-olefin comonomers having 4 to 10 carbon atoms, namely 1-butene and 1-hexene.
[0173] Preferably, the total amount of comonomers present in the multimodal ethylene terpolymer (II) is 0.5 mol% to 10 mol%, more preferably 1 mol% to 8 mol%, even more preferably 1 mol% to 5 mol%, even more preferably 1.5 mol% to 5 mol%, and most preferably 2.5 mol% to 4 mol%.
[0174] The preferred bimodal terpolymer multimodal ethylene terpolymer (II) preferably comprises an ethylene polymer component (A1) and an ethylene polymer component (B1), or is composed of an ethylene polymer component (A1) and an ethylene polymer component (B1), wherein the ethylene polymer component (A1) has a higher MFR2 than the ethylene polymer component (B1).
[0175] Preferably, the ethylene polymer component (A1) has an MFR2 of 1 g / 10 min to 50 g / 10 min, more preferably 1 g / 10 min to 40 g / 10 min, even more preferably 1 g / 10 min to 30 g / 10 min, even more preferably 2 g / 10 min to 20 g / 10 min, even more preferably 2 g / 10 min to 15 g / 10 min, and most preferably 2 g / 10 min to 10 g / 10 min.
[0176] The ratio of the MFR2 of the ethylene polymer component (A1) to the MFR2 of the ethylene polymer component (B1) is 2 to 50, preferably 5 to 40, more preferably 10 to 30, even more preferably 10 to 25, and most preferably 11 to 25.
[0177] Preferably, the ethylene polymer component (A1) contains a comonomer that is different from that of the ethylene polymer component (B1).
[0178] Preferably, the ethylene polymer component (A1) has a lower amount (mol%) of comonomers than the ethylene polymer component (B1). More preferably, the ratio of [the amount (mol%) of α-olefin comonomers having 4 to 10 carbon atoms present in the ethylene polymer component (A1)] to [the amount (mol%) of at least two α-olefin comonomers having 4 to 10 carbon atoms in the final multimodal ethylene terpolymer] is 0.10 to 0.60, preferably 0.15 to 0.50.
[0179] Preferably, the α-olefin comonomer having 4 to 10 carbon atoms in the ethylene polymer component (A1) is 1-butene, and the α-olefin comonomer having 4 to 10 carbon atoms in the ethylene polymer component (B1) is 1-hexene.
[0180] Preferably, the ethylene polymer component (A1) has a density different from that of the ethylene polymer component (B1), and more preferably has a higher density than that of the ethylene polymer component (B1).
[0181] The density of the ethylene polymer component (A1) is preferably 925 kg / m³. 3 Up to 950kg / m 3 More preferably 930 kg / m 3 Up to 945kg / m 3.
[0182] Preferably, based on the total amount (100 wt.%) of the multimodal ethylene terpolymer, the multimodal ethylene terpolymer contains 30 wt.% to 70 wt.%, more preferably 40 wt.% to 60 wt.%, even more preferably 35 wt.% to 50 wt.%, and still more preferably 40 wt.% to 50 wt.% of an ethylene polymer component (A1); and 70 wt.% to 30 wt.%, more preferably 60 wt.% to 40 wt.%, even more preferably 50 wt.% to 65 wt.%, and still more preferably 50 wt.% to 60 wt.% of an ethylene polymer component (B).
[0183] Most preferably, the multimodal ethylene terpolymer (II) is composed of ethylene polymer components (A1) and (B1) as the sole polymer components. Accordingly, the ratio between the ethylene polymer components (A1) and (B1) is (30 to 70):(70 to 30), preferably (40 to 60):(60 to 40), more preferably (35 to 50):(65 to 50), and even more preferably (40 to 50):(60 to 50).
[0184] In a particularly preferred embodiment, the multimodal ethylene terpolymer (II) is a bimodal terpolymer, i.e., comprising low molecular weight and high molecular weight components, and having an MFR2 of 1.2 g / 10 min to 1.8 g / 10 min, and / or an MFR5 of 3.0 g / 10 min to 5.0 g / 10 min, and / or an MFR5 of 20 g / 10 min to 40 g / 10 min. 21 and / or 915 kg / m 3 Up to 920kg / m 3 The density, and / or molecular weight distribution (MWD) of 3.0 to 5.0, and / or MnO of 15 kg / mol to 25 kg / mol. n And / or M from 80 kg / mol to 115 kg / mol w and / or 15 to 25 MFR 21 / MFR2 ratio (FRR) 21 / 2 ), and / or 6 to 9 MFR 21 / MFR5 ratio (FRR) 21 / 5 ).
[0185] Preferred multimodal ethylene terpolymers (II) are also commercially available products, such as Anteo from Borealis or Borouge. TM It possesses the characteristics required in this article, especially Anteo. TM FK1828 or Anteo TMFK1820.
[0186] Preferably, based on the total weight of the inner layer C composition, the component AC is present in the inner layer C composition in an amount of 50 wt.% to 95 wt.%, more preferably 60 wt.% to 90 wt.%, and most preferably 70 wt.% to 85 wt.%.
[0187] The AC component is particularly suitable for imparting a low sealing initiation temperature to the sealing film while maintaining good optical performance.
[0188] Component BC
[0189] The inner layer C composition may further include component BC. Preferably, component BC is a low-density ethylene polymer (LDPE), preferably having a density of 918 kg / m³. 3 Up to 928kg / m 3 The low-density ethylene polymer with a density of 1.5 g / 10 min to 2.5 g / 10 min (MFR2) (as determined according to ISO 1133), as described for component CG of the inner layer G composition.
[0190] All embodiments described for component CG are embodiments of component BC. Component BC can be independently selected from any of these embodiments, and the selected embodiments may be the same or different for BC and CG.
[0191] Preferably, based on the total weight of the inner layer C composition, the component BC is present in the inner layer C composition in an amount of 5 wt.% to 50 wt.%, more preferably in an amount of 10 wt.% to 30 wt.%.
[0192] In one embodiment, the inner layer C composition comprises, or is composed of, any of the components AC and BC described in the above embodiments.
[0193] In a preferred embodiment, based on the total weight of the inner layer C composition, the inner layer C composition comprises, or consists of, the following components: component AC in an amount of 50 wt.% to 95 wt.%, preferably 70 wt.% to 85 wt.%, and component BC in an amount of 5 wt.% to 50 wt.%, preferably 15 wt.% to 30 wt.%.
[0194] Core layer B
[0195] The core layer B of the sealing membrane is composed of a core layer B composition containing components that particularly contribute to the membrane's stiffness and other mechanical properties such as dart impact resistance and tear resistance.
[0196] Component AB
[0197] The core layer B may comprise component AB. Preferably, component AB is a medium-density polyethylene polymer (MDPE), preferably having a density of 925 kg / m³. 3 Up to 945kg / m 3 Medium-density ethylene polymers with a density of 0.05 g / 10 min to 0.50 g / 10 min and a melt flow rate (MFR2) (as determined according to ISO 1133).
[0198] This type of MDPE is well known in the art and is typically produced in polymerization processes using catalysts.
[0199] The MDPE of component AB is preferably a multi-peak MDPE, and more preferably a bi-peak MDPE. For example, such a multi-peak MDPE and its production are described on pages 8 to 10 of WO 2017 / 021389A1, see reference to that document.
[0200] Preferably, the MDPE of component AB has a strength of 930 kg / m³. 3 Up to 940kg / m 3 More preferably 932kg / m 3 Up to 938kg / m 3 The density of component AB is preferably higher than that of component AC.
[0201] Preferably, the MDPE of component AB is an ethylene copolymer. The comonomer can be an α-olefin having 4 to 12 carbon atoms, such as 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, or 1-decene. More preferably, the MDPE is a copolymer of ethylene with 1-butene or 1-hexene, and most preferably a copolymer of ethylene with 1-butene.
[0202] Preferably, the total amount of comonomers present in the MDPE of component AB is 1.0 mol% to 4.0 mol%, more preferably 1.5 mol% to 3.5 mol%, and most preferably 2.0 mol% to 3.2 mol%.
[0203] Preferably, the MDPE of component AB has an MFR2 of 0.06 g / 10 min to 0.35 g / 10 min, more preferably 0.08 g / 10 min to 0.30 g / 10 min, and most preferably 0.10 g / 10 min to 0.30 g / 10 min.
[0204] Preferably, the MDPE of component AB has an MFR5 of 0.35 g / 10 min to 1.2 g / 10 min, more preferably 0.37 g / 10 min to 1.00 g / 10 min, and most preferably 0.40 g / 10 min to 0.80 g / 10 min.
[0205] In a particularly preferred embodiment, the MDPE of component AB has an MFR2 of 0.10 g / 10 min to 0.20 g / 10 min, and / or an MFR5 of 0.40 g / 10 min to 0.80 g / 10 min, and / or an MFR5 of 10 g / 10 min to 20 g / 10 min. 21 and / or 932 kg / m 3 Up to 938kg / m 3 The density, and / or molecular weight distribution (MWD) of 15 to 35, and / or Mn of 8 kg / mol to 12 kg / mol n And / or M from 150 kg / mol to 280 kg / mol w and / or 80 to 150 MFR 21 / MFR2 ratio (FRR) 21 / 2 ), and / or 20 to 30 MFR 21 / MFR5 ratio (FRR) 21 / 5 All molecular weight parameters were determined using standard GPC methods in standard calibration, as described in further detail below.
[0206] For MDPE as component AB, resin Borstar FB1350 produced by companies such as Borealis or Borouge can be used.
[0207] Preferably, based on the total weight of the core layer B composition, component AB is present in the core layer B composition in an amount of 35 wt.% to 80 wt.%, more preferably 40 wt.% to 75 wt.%, and most preferably 50 wt.% to 70 wt.%.
[0208] The component AB specifically imparts high stiffness to the core layer B.
[0209] Component BB
[0210] The core layer B composition may include component BB. Preferably, component BB is a linear low-density ethylene polymer (LLDPE), more preferably having a density of 915 kg / m³. 3 Up to 925kg / m 3A linear low-density ethylene polymer with a density and a melt flow rate (MFR2) of 0.5 g / 10 min to 2.0 g / 10 min (as determined according to ISO 1133), as described for component AC of the inner layer C composition.
[0211] All embodiments described for component AC are embodiments of component BB. Component BB can be independently selected from any of these embodiments, and the selected embodiments may be the same or different for BB and AC.
[0212] Preferably, based on the total weight of the core layer B composition, the component BB is present in the core layer B composition in an amount of 15 wt.% to 45 wt.%, more preferably in an amount of 20 wt.% to 40 wt.%.
[0213] In particular, in combination with component AB, component BB contributes to the high dart impact resistance and good stiffness of the sealing membrane.
[0214] Component CB
[0215] The core layer composition may include component CB. Preferably, the component CB is a low-density ethylene polymer (LDPE), preferably having a density of 918 kg / m³. 3 Up to 928kg / m 3 The low-density ethylene polymer with a density and a melt flow rate (MFR2) of 1.5 g / 10 min to 2.5 g / 10 min (as determined according to ISO 1133), as described for component CG of the inner layer G composition.
[0216] All embodiments described for component CG are embodiments of component CB. Component CB can be independently selected from any of these embodiments, and the selected embodiments may be the same or different for CB and CG.
[0217] Preferably, based on the total weight of the inner layer B composition, the component CB is present in the core layer B composition in an amount of 5 wt.% to 15 wt.%, more preferably in an amount of 7 wt.% to 13 wt.%.
[0218] In one embodiment, the core layer B composition comprises, or is composed of, any of the components AB and BB in the above embodiments and optional CB.
[0219] In a preferred embodiment, based on the total weight of the core layer B composition, the core layer B composition comprises, or is composed of, the following components: component AB in an amount of 50 wt.% to 75 wt.%, component BB in an amount of 25 wt.% to 40 wt.%, and optional component CE in an amount of 0 wt.% to 15 wt.%.
[0220] Outer layer A
[0221] The outer layer A of the sealing film is composed of an outer layer A composition containing one or more components. In a laminated film, the outer layer E can be disposed between the core layer B and the outer layer E of the printed film, and it contributes to the mechanical and optical properties of the film.
[0222] Component AA
[0223] The outer layer composition may contain component AA. Preferably, component AA is a linear low-density ethylene polymer (LLDPE), preferably having a density of 915 kg / m³. 3 Up to 930kg / m 3 A linear low-density ethylene polymer with a density of 0.05 g / 10 min to 1.0 g / 10 min (MFR2) (determined according to ISO 1133), as described for component BG1 of the inner layer G composition.
[0224] All embodiments described for component BG1 are embodiments of component AA. Component AA can be independently selected from any of these embodiments, and the selected embodiments can be the same or different for AA and BG1.
[0225] Preferably, based on the total weight of the outer layer A composition, the component AA is present in the outer layer A composition in an amount of 25 wt.% to 55 wt.%, more preferably in an amount of 35 wt.% to 50 wt.%.
[0226] Component BA
[0227] The outer layer composition may contain component BA. Preferably, component BA is a linear low-density ethylene polymer (LLDPE), preferably having a density of 915 kg / m³. 3 Up to 925kg / m 3 A linear low-density ethylene polymer with a density and a melt flow rate (MFR2) of 0.5 g / 10 min to 2.0 g / 10 min (as determined according to ISO 1133), as described for component AC of the inner layer C composition.
[0228] All embodiments described for component AC are embodiments of component BA. Component BA can be independently selected from any of these embodiments, and the selected embodiments may be the same or different for BA and AC.
[0229] Preferably, based on the total weight of the outer layer A composition, the component BA is present in the outer layer A composition in an amount of 25 wt.% to 55 wt.%, more preferably in an amount of 30 wt.% to 50 wt.%.
[0230] Component CA
[0231] The outer layer A composition may include component CA. Preferably, component CA is a low-density ethylene polymer (LDPE), preferably having a density of 918 kg / m³. 3 Up to 928kg / m 3 The low-density ethylene polymer with a density and a melt flow rate (MFR2) of 1.5 g / 10 min to 2.5 g / 10 min (as determined according to ISO 1133), as described for component CG of the inner layer G composition.
[0232] All embodiments described for component CG are embodiments of component CA. Component CA can be independently selected from any of these embodiments, and the selected embodiments may be the same or different for CA and CG.
[0233] Preferably, based on the total weight of the outer layer A composition, the component CA is present in the outer layer A composition in an amount of 5 wt.% to 35 wt.%, more preferably in an amount of 10 wt.% to 30 wt.%.
[0234] In one embodiment, the outer layer A composition comprises, or is composed of, any of the components AA and BA in the above embodiments and optional CA.
[0235] In a preferred embodiment, based on the total weight of the outer layer A composition, the outer layer A composition comprises, or is composed of, the following components: component AA in an amount of 30 wt.% to 50 wt.%; component BA in an amount of 30 wt.% to 50 wt.%; and optional component CA in an amount of 0 wt.% to 30 wt.%.
[0236] Specific implementation methods of sealing membrane
[0237] The present invention also relates to a sealing film. In one specific embodiment, the present invention relates to a sealing film comprising an outer layer A, a core layer B, and an inner layer C, wherein the inner layer C is composed of an inner layer C composition comprising the following components:
[0238] a) Component AC, which is a linear low-density ethylene polymer with a density of 915 kg / m³. 3 Up to 925kg / m 3 The density and melt flow rate (MFR2) from 0.5 g / 10 min to 2.0 g / 10 min were determined according to ISO 1133; and
[0239] b) Component BC, which is low-density polyethylene with a density of 918 kg / m³. 3 Up to 928kg / m 3 The density and melt flow rate (MFR2) of the inner layer C composition, determined according to ISO 1133, are preferably 10 wt.% to 30 wt.% based on the total weight of the composition.
[0240] It meets at least one of the following criteria:
[0241] c) Core layer B is composed of a core layer B composition containing component AB, wherein component AB is medium-density polyethylene with a density of 925 kg / m³. 3 Up to 945kg / m 3 The density and melt flow rate (MFR2) of the core layer B composition, determined according to ISO 1133, are preferably 40 wt.% to 75 wt.% based on the total weight of the core layer B composition; and
[0242] d) Outer layer A is composed of an outer layer A composition containing component AA, wherein component AA is a linear low-density ethylene polymer having a density of 915 kg / m³. 3 Up to 930kg / m 3 The density and melt flow rate (MFR2) of the outer layer A composition, as determined according to ISO 1133, are preferably 30 wt.% to 50 wt.% based on the total weight of the outer layer A composition.
[0243] In one implementation, criterion c) is satisfied. In another implementation, criterion d) is satisfied. In yet another implementation, both criteria c) and d) are satisfied.
[0244] Preferably, based on the total weight of the inner layer C composition, the component AC is present in the inner layer C composition in an amount of 50 wt.% to 95 wt.%, more preferably 60 wt.% to 90 wt.%, and most preferably 70 wt.% to 85 wt.%.
[0245] The components AC, BC, and AB can be selected from any of the above embodiments.
[0246] The inner layer C composition may also contain any of the components CC described in the above embodiments.
[0247] The aforementioned core layer B composition and outer layer A composition may contain additional components for specific layers of the sealing film as described above.
[0248] performance
[0249] The sealing membrane is characterized by its relatively high stiffness (i.e., tensile modulus of 300 MPa to 500 MPa), high drop impact resistance (i.e., high DDI), and other tensile properties. The sealing membrane exhibits excellent sealing performance through its low seal initiation temperature and hot tack temperature (i.e., SIT below 95°C). These properties can be achieved by using component AC in the sealing membrane and can be further improved by the presence of component BC in the inner layer C. Furthermore, the presence of components AA and AB in the corresponding other layers A and B of the sealing membrane (and even more so with components BA and BB) also contributes to the excellent performance of the sealing membrane.
[0250] Preferably, when measured at the inner layer C of the sealing membrane, the sealing membrane has a seal initiation temperature (SIT) of less than 100°C, preferably less than 95°C, at 5N. Preferably, when measured at the inner layer C of the sealing membrane, the membrane has a seal initiation temperature (SIT) of 80°C to 100°C, preferably 85°C to 95°C, at 5N. The seal initiation temperature (SIT) at 5N is determined according to ASTM F 2029 and ASTM F 88.
[0251] Preferably, the sealing film has a tensile modulus (1% secant modulus) of 280 MPa to 600 MPa, more preferably 300 MPa to 500 MPa, in the machine direction (MD). The tensile modulus (1% secant modulus) in the machine direction (MD) is determined according to ASTM D882.
[0252] Preferably, the sealing film has a haze value of less than 12%, more preferably less than 10%. Preferably, the sealing film has a haze value of 3% to 12%, more preferably 5% to 10%. The haze value is determined according to ASTM D1003 as a measure of the film's transparency, and this value indicates good transparency.
[0253] Preferably, the sealing film has a gloss value of at least 80, more preferably at least 90. Preferably, the sealing film has a gloss value of 80 to 140, more preferably 90 to 130. The gloss value (GU) is measured at 60° according to ISO 2813 on the inner layer C or the outer layer A, preferably on the inner layer C.
[0254] Preferably, the sealing membrane has a dart impact (DDI) of at least 200g, more preferably at least 210g. Preferably, the sealing membrane has a dart impact (DDI) of 200g to 600g, more preferably 210g to 550g. The dart impact is determined according to ASTM D1709 "Method A", preferably on a sealing membrane with a thickness of 35μm to 120μm, more preferably 40μm to 110μm, and most preferably 40μm to 100μm.
[0255] polyethylene laminate
[0256] structure
[0257] In this invention, the polyethylene laminated film comprises, or is composed of, any of the sealing film and printing film described in the above embodiments, and the sealing film and printing film are laminated together.
[0258] The laminated film includes an inner surface and an outer surface, wherein the inner layer G of the printed film forms the outer surface of the laminated film, and the inner layer C of the sealing film forms the inner surface of the laminated film.
[0259] In the laminated film, the printed film and the sealing film are connected to each other through their outer layers E and A, and these layers form the intermediate layer of the laminated film. In other words, the outer layer A of the sealing film is laminated to the outer layer E of the printed film.
[0260] The bonding, i.e., the lamination of the printed film and the sealing film to each other, can be affected by any conventional lamination apparatus using any conventional lamination method, such as adhesive lamination, including solvent-based and solvent-free adhesive lamination using any conventional commercially available adhesives. The adhesive can be applied to the sealing film and / or the printed film in any suitable manner. For example, the method may include using a laminator, gravure coating, roller coating, wire rod coating, spray coating, etc. One or more film surfaces to which the adhesive is applied may be corona treated to increase surface energy and provide sufficient wettability for the adhesive components.
[0261] Lamination can optionally be performed without any binder, such as sandwich lamination with or without a fused mesh, which can be pressed between the films. This fused mesh can be any conventional polyethylene-based fused mesh material, such as LDPE. Lamination can be further performed via extrusion coating technology. All of these lamination methods are well known in the art and described in the literature.
[0262] Preferably, lamination is performed using an adhesive (e.g., a solvent-free adhesive). The adhesive may form a layer (e.g., between layer E and layer A) Figure 1 Adhesive layer D in the middle.
[0263] Preferably, the adhesive has a concentration of 1.0 g / m³. 2 Up to 3.5g / m 2 More preferably 1.2g / m 2 Up to 2.5g / m 2 The weight per square meter.
[0264] Preferably, the adhesive (or adhesive layer) comprises less than 5 wt.% of the total weight of the laminate. The percentage of adhesive typically depends on the total weight of the laminate, which is related to the thickness of the laminate. For example, based on the total weight of the laminate, a laminate of about 75 μm preferably contains up to 4 wt.% adhesive, while a laminate of about 130 μm preferably contains up to 3 wt.% adhesive.
[0265] Preferably, the laminated film has a thickness of 50 μm to 160 μm, more preferably 55 μm to 145 μm, and most preferably 60 μm to 130 μm.
[0266] The laminated film is a "polyethylene film" as defined above for the printed film. The use of polyethylene film provides a fully recyclable and sustainable packaging structure. Therefore, it is particularly preferred that the printed film and sealing film are polyethylene films, containing at least 90 wt.%, more preferably at least 95 wt.%, and most preferably at least 98 wt.%, of an ethylene polymer (which comprises ethylene homopolymer and copolymers of ethylene with one or more C3 to C12 α-olefins) based on the total weight of their respective films. Preferably, neither the printed film nor the sealing film contains a non-polyolefin polymer, such as polyester or polyamide. Nevertheless, the laminated film may contain a non-polyolefin polymer (e.g., polyurethane adhesive) in the adhesive layer, which preferably comprises less than 5 wt.% of the total weight of the laminated film.
[0267] The base film is typically reverse-printed, meaning it is printed on the outer layer E of the base film, which is then laminated with the outer layer A of the sealing film, as shown below. Figure 1 As shown, the outer layers E and A form the core / intermediate layer of the laminated film.
[0268] performance
[0269] The laminated film according to the invention has improved mechanical properties as well as good optical and excellent barrier properties. With improved heat resistance, the laminated film can run smoothly on high-speed VFFS machines. Generally, for subsequent use in the VFFS production line, a higher SIT in the printed film on the sealing film is required to avoid sealing clamp adhesion problems, which is closely related to δSIT (also known as the SIT gap between the inner and outer surfaces of the laminate).
[0270] The composition of the inner layers G and C of the printed film and the sealing film is selected in such a way that the sealing initiation temperature (SIT) of the outer surface of the laminate at 5N is at least 10°C higher than the sealing initiation temperature of the inner surface of the laminate at 5N, preferably at least 11°C higher, more preferably at least 12°C higher, said sealing initiation temperature being determined according to ASTM F2029 and ASTM F88.
[0271] Preferably, the sealing initiation temperature (SIT) of the outer surface of the laminate at 5N is 10°C to 30°C higher than that of the inner surface of the laminate at 5N, more preferably 12°C to 25°C higher.
[0272] This temperature difference between the two outer layers of the laminate allows the laminate to be packaged at a speed of 50 bags / minute to 80 bags / minute without any clamping or sticking issues at the sealing strip in the VFFS production line.
[0273] Preferably, when measured on the outer surface of the laminate (i.e., the inner layer G), the outer surface of the laminate has a seal initiation temperature (SIT) of at least 105°C, preferably at least 110°C, at 5N. Preferably, when measured on the outer surface of the laminate (i.e., the inner layer G), the film has a seal initiation temperature (SIT) of 105°C to 125°C, preferably 110°C to 125°C, at 5N. The seal initiation temperature (SIT) at 5N is determined according to ASTM F 2029 and ASTM F 88.
[0274] Preferably, when measured on the inner surface of the laminate (i.e., inner layer C), the inner surface of the laminate has a seal initiation temperature (SIT) of less than 110°C at 5N, more preferably less than 105°C. Preferably, when measured on the inner surface of the laminate (i.e., inner layer C), the film has a seal initiation temperature (SIT) of 80°C to 110°C at 5N, more preferably 85°C to 105°C, and even more preferably 85°C to 100°C. The seal initiation temperature (SIT) at 5N is determined according to ASTM F 2029 and ASTM F 88.
[0275] It should be noted that any of the above-mentioned ranges of the sealing initiation temperature (SIT) of the inner surface of the laminate at 5N can be combined with any of the above-mentioned ranges of the sealing initiation temperature (SIT) of the outer surface of the laminate at 5N.
[0276] Another important parameter used to determine membrane stiffness is tensile strength / 1% secant modulus. The secant modulus is a measure of the strength properties of the membrane's elastic region, representing the actual deformation at a selected point on the stress-strain curve. Therefore, the secant modulus provides valuable insights into stiffness and elongation in use, or how the membrane can stretch under subsequent printing and packaging operations (such as forming, filling, and sealing (FFS) machines) and / or under normal use tension in the packaging. Thus, stiffness is critical for any polyethylene film.
[0277] Preferably, the laminate has a tensile modulus (1% secant modulus) of 400 MPa to 800 MPa, more preferably 400 MPa to 600 MPa, in the machine direction (MD). The tensile modulus (1% secant modulus) in the machine direction (MD) is determined according to ASTM D882.
[0278] Preferably, the sealing film has a tensile modulus (1% secant modulus) of 280 MPa to 600 MPa, more preferably 300 MPa to 500 MPa, in the machine direction (MD). The tensile modulus (1% secant modulus) in the machine direction (MD) is determined according to ASTM D882.
[0279] Preferably, the printed film has a tensile modulus (1% secant modulus) of 500 MPa to 1000 MPa, more preferably 600 MPa to 800 MPa, in the machine direction (MD). The tensile modulus (1% secant modulus) in the machine direction (MD) is determined according to ASTM D882.
[0280] It has been found that improved laminate performance for high-speed FFS packaging can be achieved by using high-stiffness (e.g., 400 MPa to 600 MPa) polyethylene laminates produced from sealing films that have been developed in sealing layers with excellent stiffness (e.g., 300 MPa to 500 MPa) and low SIT (e.g., below 95°C), and when laminated with printed films that have excellent heat resistance (high SIT) and high stiffness (e.g., 500 MPa to 1000 MPa) and good optical properties (i.e., haze and gloss).
[0281] Preferably, the laminated film has a haze value of less than 12%, more preferably less than 10%. Preferably, the laminated film has a haze value of 3% to 12%, more preferably 5% to 10%. The haze value is determined according to ASTM D1003 and serves as a measure of the film's transparency, indicating good transparency.
[0282] Preferably, either or both of the printed film and the sealing film have a haze value of less than 12%, more preferably less than 10%. Preferably, either or both of the printed film and the sealing film have a haze value of 3% to 12%, more preferably 5% to 10%. The haze value is determined according to ASTM D1003 as a measure of the film's transparency, and this value indicates good transparency.
[0283] Preferably, the laminated film has a gloss value of at least 80, more preferably at least 90. Preferably, the film has a gloss value of 80 to 140, more preferably 90 to 130. The gloss value (GU) is measured at 60° according to ISO 2813 at the inner layer C or G, preferably at the inner layer G, which is the outer surface of the laminated film.
[0284] Preferably, either or both of the printed film and the sealing film have a gloss value of at least 80, more preferably at least 90. Preferably, either or both of the printed film and the sealing film have a gloss value of 80 to 140, more preferably 90 to 130. The gloss value (GU) is measured at 60° according to ISO 2813 at the inner layer C / G or the outer layer A / E, preferably at the inner layer G and / or C.
[0285] Excellent barrier properties (e.g., less than 4.0 g / m³) are achieved in the laminate without the use of barrier coatings or metallization. 2 ( / day water vapor resistance). Therefore, the laminated film according to the present invention has good barrier properties, of which moisture barrier is the most important.
[0286] Preferably, the laminated film has a density of not more than 5 g / m³. 2 / d, preferably not greater than 5g / m 2 / d water vapor transmission rate (WVTR). Preferably, the laminated film has a water vapor transmission rate of 1 g / m³. 2 / d to 4g / m 2 / d, more preferably 1.5g / m 2 / d to 4.5g / m 2 / d water vapor transmission rate (WVTR). The water vapor transmission rate (WVTR) was measured according to ASTM F-1249 at 37.8°C and 90% RH.
[0287] Preferably, the laminated film has a diameter of not more than 2000 cm. 3 / m 2 / d, preferably not greater than 1800cm 3 / m 2 The oxygen permeability (OTR) is 600 cm² / day. Preferably, the laminated film has an OTR of 600 cm² / day. 3 / m2 / d to 2000cm 3 / m 2 / d, more preferably 800cm 3 / m 2 / d to 1800cm 3 / m 2 / d of oxygen transmission rate (OTR). The oxygen transmission rate (OTR) was determined according to ISO 15105-2 at 23°C and 0% RH.
[0288] Other properties of the laminated film are:
[0289] Preferably, the laminate has a tensile modulus (1% secant modulus) of 500 MPa to 1200 MPa, more preferably 550 MPa to 1000 MPa, in the transverse direction (TD). The tensile modulus (1% secant modulus) in the transverse direction (TD) is determined according to ASTM D882.
[0290] Preferably, the laminate has a tensile stress at break of 40 MPa to 80 MPa, more preferably 45 MPa to 70 MPa, in the machine direction (TD). Preferably, the laminate has a tensile stress at break of 25 MPa to 60 MPa, more preferably 27 MPa to 50 MPa, in the transverse direction (TD).
[0291] Preferably, the laminate has an elongation at break of 350% to 700%, more preferably 400% to 650%, in the machine direction (TD). Preferably, the laminate has an elongation at break of 450% to 900%, more preferably 500% to 800%, in the transverse direction (TD).
[0292] The parameters of tensile stress at break and elongation at break were determined according to ISO 527-3.
[0293] Preferably, the laminate has a tear strength (Elmendorf) of 2.0 N to 15.0 N in the machine direction (MD), more preferably 2.2 N to 10.0 N. Preferably, the laminate has a tear strength (Elmendorf) of 20.0 N to 50.0 N in the transverse direction (TD), more preferably 23.0 N to 45.0 N. The tear strength (Elmendorf) is determined according to ASTM D 1922.
[0294] Preferably, the laminate has a dart impact (DDI) of at least 200 g, more preferably at least 210 g. Preferably, the laminate has a dart impact (DDI) of 200 g to 600 g, more preferably 210 g to 550 g. The dart impact is determined according to ASTM D1709 "Method A", preferably on a laminate with a thickness of 50 μm to 160 μm, more preferably 55 μm to 145 μm, and most preferably 60 μm to 130 μm.
[0295] Preferably, the laminated film has a coefficient of friction of less than 0.60, more preferably less than 0.50. Preferably, the laminated film has a coefficient of friction of 0.10 to 0.50, more preferably 0.15 to 0.48. The coefficient of friction is determined according to ISO 8295 under dynamic conditions (inner / inner or outer / outer).
[0296] In one embodiment, the seal initiation temperature (SIT) of the outer surface of the laminate at 5 N, as determined by ASTM F 2029 and ASTM F 88, is 10° to 30° higher than that of the inner surface of the laminate at 5 N. At the inner layer G, the gloss value of the film is at least 80, as determined by ISO 2813 at 60°. Optionally, the tensile modulus (1% secant modulus) of the film in the machine direction (MD) is 400 MPa to 800 MPa, as determined by ASTM D882.
[0297] preparation
[0298] Any sealing and printed films of the laminated film are typically prepared using conventional processes for preparing multilayer films, wherein the layers of the film are co-extruded.
[0299] The different polymer components in any layer of the film are typically thoroughly mixed before layer formation, for example using a twin-screw extruder, preferably a counter-rotating or co-rotating extruder. The blend is then converted into a co-extruded film.
[0300] The membrane can be produced by blown film or casting processes. To manufacture such a multilayer membrane, typically at least two polymers are melted and extruded simultaneously (i.e., co-extruded) through a multichannel tubular, annular, or circular die to form a tube, which is then inflated, expanded, and / or cooled by air (or a combination of gases) to form a membrane. Blown film manufacturing is a well-known process.
[0301] The blow molding (co)extrusion can be carried out in a temperature range of 150°C to 230°C, more preferably 160°C to 225°C, and cooled by blowing (usually air) at a temperature of 10°C to 40°C, preferably 12°C to 16°C, to provide a frosting height of 0.5 to 4 times the mold diameter, more preferably 1 to 2 times.
[0302] The blow-up ratio (BUR) should generally be in the range of 1.5 to 3.5, preferably 2.0 to 3.0, and more preferably 2.1 to 2.8.
[0303] Since the sealing film and the printing film are preferably non-oriented films, they are preferably not subjected to a stretching step to obtain possible orientation.
[0304] A laminated film is prepared from a sealing film and a printed film using the lamination process described above.
[0305] Products & Uses
[0306] The present invention also relates to an article comprising a polyethylene laminate according to the present invention. Preferred articles are packaging articles, such as pouches (e.g., stand-up pouches), sacks, bags, sachets, or lamitubes.
[0307] The present invention also relates to the use of polyethylene laminates according to the invention for product packaging. In particular, they can be used in (vertical) forming, filling and sealing packaging technologies, or for the formation of pouches (such as stand-up pouches), large bags, bags, sealed pouches or laminar flow tubes.
[0308] Specific products and uses include heavy-duty transport bags, detergent bags, and packaging for various food and non-food products / uses, such as rice, wheat, grains, flour, cereals, and pet food, and non-food products such as detergents / laundry powder, building materials, chemicals, and other materials.
[0309] Any embodiment of the invention described herein may be combined with one or more of these embodiments. In particular, any embodiment described for the polyethylene laminate of the invention is applicable to the use of the polyethylene laminate or article thereof.
[0310] Furthermore, the present invention relates to an article comprising the sealing film, and to the use of the sealing film in packaging articles, as described above for laminated films. Attached Figure Description
[0311] In the following description, the present invention will be further illustrated by way of embodiments with reference to the following figures:
[0312] Figure 1 The structure of a laminate according to one embodiment of the present invention.
[0313] Figure 2 : The initial sealing temperature of the sealing membrane.
[0314] Figure 3 : The initial sealing temperature of the printed film. Detailed Implementation
[0315] Measurement and determination methods
[0316] Unless otherwise defined, the definitions of the following terms and measurement methods apply to the above general description of the invention and the following embodiments.
[0317] a) Determination of melt flow rate (MFR)
[0318] Melt flow rate (MFR) was determined according to ISO 1133 and expressed in g / 10 min. A higher melt flow rate corresponds to a lower polymer viscosity. The MFR of polyethylene was determined at 190°C with loadings of 2.16 kg (MFR2), 5.00 kg (MFR5), or 21.6 kg (MFR6). 21 ).
[0319] The flow rate ratio (FRR) is an indicator of molecular weight distribution and represents the ratio of flow rates under different loads. Therefore, FRR... 21 / 5 MFR 21 The value of / MFR5.
[0320] b) Density
[0321] According to ISO 1183-1:2004 (Method A), the density of the polymer is measured on a compression-molded specimen prepared according to ISO 17855-2, in kg / m³. 3 Provided.
[0322] c) GPC
[0323] 1) GPC Conventional Method
[0324] According to ISO 16014-1:2003, ISO 16014-2:2003, ISO 16014-4:2003 and ASTM D6474-12, the following formula is used to determine the average molecular weight (M) by gel permeation chromatography (GPC). z M w and M n Molecular weight distribution (MWD) and its width are described by the polydispersity index (PDI) = M w / M n (where M) n M is the number average molecular weight. w (Weight-average molecular weight):
[0325]
[0326] For a constant elution volume interval ΔV i A iand M i The peak slice area and the molecular weight (MW) of the polyolefin are respectively compared with the elution volume V. i The correlation is given by N, where N equals the number of data points obtained from the chromatogram between the integration limits.
[0327] A high-temperature GPC system equipped with an infrared (IR) detector (PolymerChar IR4 or IR5 from Valencia, Spain) or a differential refractometer (RI) from Agilent Technologies, and featuring 3×Agilent-PLgel Olexis and 1×Agilent-PLgel Olexis Guard columns, was used. 250 mg / L of 2,6-di-tert-butyl-4-methylphenol-stabilized 1,2,4-trichlorobenzene (TCB) was used as the mobile phase. The chromatographic system was run at a column temperature of 160 °C, a detector temperature of 160 °C, and a constant flow rate of 1 mL / min. 200 μL of sample solution was injected for each analysis. Data collection was performed using Agilent Cirrus version 3.3 software or PolymerChar GPC-IR control software.
[0328] The column assembly was calibrated using 19 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. The PS standards were dissolved at room temperature for several hours. The conversion of the polystyrene peak molecular weight to the polyolefin molecular weight was performed using the Mark-Houwink equation and the following Mark-Houwink constant:
[0329] K PS =19 x 10 -3 mL / g, α PS =0.655
[0330] K PE =39 x 10 -3 mL / g, α PE =0.725
[0331] The calibration data were fitted using a third-order polynomial fitting method.
[0332] All samples were prepared at concentrations of approximately 1 mg / mL, and PE was dissolved in freshly distilled TCB at 160°C for 3 hours, with the TCB stabilized by continuous gentle shaking with 250 ppm Irgafos 168.
[0333] 2) GPC viscosity method
[0334] The average molecular weight (M) of LDPE was determined using the universally calibrated GPC-viscosity method.z M w and M n The molecular weight (MWD) and molecular weight distribution were determined according to ISO 16014-4 2019 using gel permeation chromatography (GPC). w M n Molecular weight distribution (MWD) and its width are described by the polydispersity index (PDI) = M w / M n (where M) n M is the number average molecular weight. w (Weight-average molecular weight). A PL 220 (Polymer Laboratories) GPC equipped with an IR4 infrared detector and four online capillary bridge viscometers (PL-BV 400-HT) was used. A 3×Olexis and 1×OlexisGuard column from Polymer Laboratories was used as the stationary phase, and 1,2,4-trichlorobenzene (TCB, stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol) was used as the mobile phase, at 160 °C and a constant flow rate of 1 mL / min. 200 μL of sample solution was injected for each analysis. The corresponding detector constant and inter-detector delay volume of the viscometer were determined using a narrow PS standard (MWD = 1.01), where the molar mass of the PS was 132900 g / mol and the intrinsic viscosity was 0.4789 dl / g. The detector constant of the IR4 detector was determined using NIST 1475a, with a dn / dc ratio of 0.094 cm⁻¹. 3 / g.
[0335] The chromatographic column assembly was calibrated using a universal calibration method (according to ISO 16014-2:2019) for at least 15 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11600 kg / mol. The intrinsic viscosity was calculated based on the corresponding concentration (IR4) of the PS standards, the online viscometer signal, and the measured polystyrene detector constant. For low molecular weight PS with a molar mass below 3000 g / mol, the initial mass concentration was used due to end-group effects in the infrared detector.
[0336] Using a universal calibration method, the molecular weight (M2) of the sample on each chromatogram can be calculated using the following formula:
[0337] logM1[η1]=V R =logM2[η2]
[0338] Where: M1 is the molar mass of PS;
[0339] η1 is the intrinsic viscosity of PS;
[0340] M2 is the molar mass of the sample;
[0341] η2 is the intrinsic viscosity of the sample;
[0342] V R To preserve volume.
[0343] All data processing and computation were performed using Cirrus Multi-Offline SEC-Software version 3.2 (Polymer Laboratories, Varian Inc.).
[0344] All samples were prepared by dissolving 5.0 mg–9.0 mg of polymer (at 160 °C) in 8 mL of stable TCB (also used as the mobile phase), for 2.5 hours for PP or 3 hours for PE, with continuous slight shaking at a maximum temperature of 160 °C.
[0345] d) Comonomer content
[0346] The content of comonomers was determined as described on pages 31 to 34 of WO2019081611.
[0347] e) Mechanical properties
[0348] Tensile modulus and tensile stress at break
[0349] According to ISO 527-3, the tensile properties of the film were determined at 23°C using a type 2 blown film specimen as shown below. According to ASTM D882, the tensile modulus in the machine direction (MD) and transverse direction (TD) was determined at 1% secant modulus at a test speed of 5 mm / min and a gauge length of 50 mm.
[0350] Tensile stress at break was measured according to ISO 527-3 Type 2 specimen, with a gauge length of 50 mm and a test speed of 500 mm / min. The membrane sample was produced according to the following "Example".
[0351] Elongation at break
[0352] According to ISO 527-3, the elongation at break in the machine direction (MD) and transverse direction (TD) was measured on the film of the thickness and production described in the "Examples" below.
[0353] Dart Impact
[0354] Dart impact (DDI) was determined on films of the thickness and production described in the following "Examples" according to ASTM D1709 "Method A".
[0355] f) Optical properties
[0356] According to ISO 2813 (gloss) and ASTM D1003 (haze and clarity), gloss, clarity, and haze were measured as optical appearance measurements of the film on the thickness and production of the film described in the "Examples" below.
[0357] The gloss of the outer and inner layers was measured at a 60° angle according to ISO 2813. According to ISO 2813, three measurement angles (20°, 60°, and 85°) can be performed using a BYK-Gardner Micro-TRI-Gloss Meter, and the gloss value at 60° is recorded and reported in gloss units (GU). Accordingly, the gloss was measured on both surfaces of the film and measured separately.
[0358] g) Coefficient of friction
[0359] According to ISO 8295, the coefficient of friction under dynamic conditions is determined, including internal / internal and external / external.
[0360] h) Sealing Initiation Temperature (SIT)
[0361] Generally, a heat seal is formed by bonding two films (polymers) together, pressing the surfaces together to form a tight contact while they are at least partially molten. This test method also covers the evaluation portion after the heat sealing process. The force required to separate the test strip containing the sealing material is measured using a UTM (also used to identify the failure mode of the specimen). Test specimens with films manufactured according to the following “Examples” are used, following ASTM F 2029 and ASTM F 88 standards, where the sealed surfaces are selected. For testing, at least five specimens should be used for each sealing temperature. The term “Seal Initiation Temperature” (SIT) is specified as “Seal Initiation Temperature at 5 N”, referring to the temperature at which a seal with a strength of 5 N is formed after cooling. The strength of the heat seal is measured at the temperature at which the heat seal is formed immediately after the sealing operation (sealing time 1.0 second, sealing pressure 3 bar for films less than 65 microns, sealing time 1.5 seconds for thicknesses of 65 microns and above), within specified time intervals (after the sealing cycle is completed and at least 24 hours after the seal has cooled to ambient temperature and reached maximum strength).
[0362] i) Temperature of hot viscosity
[0363] This test method follows ASTM F 1921 to determine the temperature required for a membrane sample to achieve a specified seal strength under specified sealing time and pressure. Therefore, the hot tack test measures the strength of the heat seal in the membrane immediately after sealing, before cooling to room temperature. For each sealing temperature, a membrane specimen with a width of 25 mm and a length >250 mm is required. According to ASTM F 1921, the hot tack temperature (°C) under 1 N of force is measured under the following conditions: sealing pressure 3 bar, residence / sealing time 1 second, cooling / delay time 100 milliseconds (release), and test / peel speed 200 mm / s for membranes smaller than 65 microns. For thicknesses of 65 microns and above, a residence / sealing time of 1.5 seconds is used under similar test conditions.
[0364] j) Water vapor transmission rate (WVTR)
[0365] The water vapor transmission rate (WVTR) of the membrane produced as described in the following “Example” was determined according to ASTM F-1249. The WVTR test was performed in accordance with ASTM F1249:2006 and / or ISO15106-2:2003 at 37.8°C and 90% relative humidity (RH).
[0366] k) Oxygen Transmission Rate (OTR)
[0367] Oxygen barrier properties, i.e., oxygen permeability, were determined on a blown membrane prepared as described below. Under ambient atmospheric pressure, the sample was installed as a sealed semi-barrier between two chambers. One chamber was slowly purged with a nitrogen stream at a given temperature and relative humidity, while the other chamber was purged with an oxygen stream at the same temperature and relative humidity as the N2 stream. As oxygen permeated through the membrane into the nitrogen carrier gas, it was delivered to a coulometric detector, where a current was generated. The magnitude of the current was proportional to the amount of oxygen flowing into the detector per unit time. The oxygen permeability (OTR) test was performed according to ISO 15105-2 at 23°C and 0% relative humidity, using 10 sccm of N2 and O2 (99.5%) gas, with a membrane surface area of 50 cm². 2 .
[0368] l) Thickness
[0369] The thickness of the membrane was determined according to ISO 4593.
[0370] Example
[0371] Three layers of sealing film and printed film have been produced, each consisting of a core layer, an inner layer, and an outer layer. Example IE1 represents the sealing film of the laminated article of the present invention, while Example CE1 is a comparative sealing film. Examples IE2 and IE3 represent the printed films of the laminated article of the present invention, with CE2 being a comparative printed film. Each sealing film has a thickness of 45 μm, and each printed film has a thickness of 27 μm. The core layer thickness of each film is 50% of the total thickness of its respective film, and the thickness of each outer layer (i.e., the inner and outer layers) is 25% of the total thickness of its respective film.
[0372] All embodiments of the invention and comparative embodiments are non-oriented films (by definition). Details of the embodiments of the invention and comparative embodiments are summarized below:
[0373] Laminated films have been produced using these sealing and printing films:
[0374] The laminated article 1 (IE4) comprises an IE1 sealing film and an IE2 printing film;
[0375] The laminated article 2 (IE5) comprises an IE1 sealing film and an IE3 printing film; and
[0376] The comparative laminate (CE3) includes CE1 sealing film and CE2 printed film.
[0377] Further details of the membrane are described in Table 1.
[0378] Table 1: Structure and composition of membranes.
[0379]
[0380]
[0381] The polymers used to make the films according to the present invention and comparative embodiments are given below.
[0382] Table 2: Properties of the polymers used in the examples.
[0383]
[0384]
[0385] test
[0386] The film preparation does not utilize specific stretching equipment; therefore, the film is produced on a standard blow molding and / or casting production line using standard film machinery systems (pressure rollers or output rollers and winding machines), and can be referred to as a "non-oriented film." The film can be formed by any suitable method through blow molding and / or casting processes, and the material forming each layer can be co-extruded using a co-extrusion feed block and die assembly to produce a film with three or more layers bonded together but with different compositions.
[0387] Any polyethylene blend used in the above-described printed film layers can be produced by any suitable conventional multilayer film extrusion line, preferably at a temperature of 150°C to 230°C, more preferably 160°C to 225°C. The conventional blown film production techniques used in this regard are, in principle, known and available to those skilled in the art. Typically, each film layer is co-extruded at a temperature range of 160°C to 225°C and cooled by blowing air at a temperature of 12°C to 16°C to provide a frosting height of 1 to 2 times the die diameter.
[0388] The blown film is produced on a Polyrema (Reifenhauser blown film production line with an internal bubble cooling system) with a capacity of 150 kg / h and a cooling air temperature between 12°C and 16°C. Details are listed in Table 3.
[0389] Table 3: Parameters of blown film production line.
[0390]
[0391] Tables 4 and 5 list the temperature distribution of the blown film production lines for sealing films and printed films, respectively, i.e., the melt temperature and respective melt pressure of the different layers used in the blown film extruder. These films were produced using standard co-extrusion machines for polyethylene, but slightly different process conditions were used for each film to optimize film aesthetics and provide stable film production.
[0392] Table 4: Process parameters of the sealing membrane.
[0393]
[0394] Table 5: Process parameters for printing film.
[0395]
[0396] Table 6 lists the temperature distribution of the blown film production line, that is, the temperature of different layers of the blown film extruder at different locations on the blown film production line.
[0397] Table 6: Temperature Distribution (°C)
[0398]
[0399] Rotary gravure printing process
[0400] All printed films in Table 1 were printed on a BOBST Rotomec 4003 10-color rotary gravure printing press. The winding tension was optimized for 27μm PE films, and a tension of 4 to 6 bar was used for smooth operation. The unwinding tension was maintained very close to the 4 to 6 bar winding tension and adjusted for reverse printing at (high) speeds exceeding 200 m / min.
[0401] Laminated product preparation
[0402] Following rotary gravure printing, the reverse-printed base film and sealing film are laminated using a solvent-free adhesive system from Henkel Corporation. The process is performed on a Nordmeccanica solvent-free laminator at a running speed of 250 m / min, using 1.7 g / m³ of adhesive. 2 The adhesive is used for lamination.
[0403] VFFS Packaging Trial
[0404] The Vertical Form Fill Seal (VFFS) machine used for producing flexible bags is a Polythermal Seal (PHS) machine from Pace Packaging (model - PaceP250 4S). Table 7 provides the operating parameters.
[0405] Table 7: VFFS operating parameters for laminated films.
[0406] Vertical sealing clamp temperature 130℃ to 135℃ 130℃ to 135℃ Sealed design Serrated 5-sealing line Serrated 5-sealing line Horizontal sealing strip temperature 120℃ to 124℃ 113℃ to 122℃ Bag production speed 40 bags / minute to 50 bags / minute 50 bags / minute to 80 bags / minute Sealing time (milliseconds) 200ms to 350ms 150ms to 250ms Cooling air Ambient temperature Ambient temperature
[0407] Membrane performance
[0408] Several properties of the laminated film were tested, including barrier properties, mechanical strength, and optical properties. The results are shown in Table 8 and discussed in the context of the properties of the sealing film and the printed film.
[0409] Table 8: Performance of Laminated Films
[0410]
[0411]
[0412] The properties of the sealing film and printed film of the laminated products are as follows.
[0413] Table 9: Sealing membrane performance (45μm PE membrane).
[0414]
[0415]
[0416] As can be seen from Table 9, compared with the CE1 sample, the IE1 sealing film has improved mechanical properties (tensile modulus, tensile strength, tensile stress at break, dart impact, tear resistance) and optical properties (haze and gloss).
[0417] The higher 1% secant modulus (300 MPa to 500 MPa) shown in Table 9 indicates that the IE1 sealing film has improved stiffness capability compared to the CE1 sealing film, meaning that the IE1 film requires more energy input to deform to the same relative extent. This is more suitable for the laminates produced.
[0418] IE1 sealing films have very high tensile and dart impact (DDI) properties, as well as good optical properties. These results are typically designed to maintain the high mechanical properties of laminates.
[0419] The coefficients of friction (COF) of both outer layers were measured under dynamic conditions and are below 0.5, making them suitable for subsequent steps, lamination, and FFS operation.
[0420] The IE1 sealing membrane shows a 30% to 40% reduction in water vapor transmission rate (WVTR), which is better moisture barrier performance than the CE1 membrane.
[0421] pass Figure 2 The relatively low seal initiation temperature and low thermotack temperature (i.e., a seal initiation temperature of less than or equal to approximately 95°C at 5N and a thermotack seal initiation temperature of less than or equal to approximately 90°C at 1N) indicate the sealing performance of the IE1 sealing film, reflecting its seal integrity performance. The sealing performance of the IE1 sealing film can improve the overall performance of the laminate because the lower SIT of the sealing layer is crucial for creating a difference in SIT or heat resistance between the sealing layer and the top layer of the printed film, and provides an advantage during packaging operations on VFFS machines (higher packaging speeds when the film is used in VFFS packaging applications).
[0422] Once the sealing film is laminated with the substrate, the SIT of the sealing layer C in the laminated article has increased to a slightly higher temperature (close to 100°C) because the total thickness of the laminated article is greater than the total thickness of a single sealing film.
[0423] Therefore, compared to CE1 sealing layers, IE1 sealing layers offer improved sealing performance, meaning that IE1 sealing films require less energy input to produce the same strength of seal as CE1 sealing films. This is particularly advantageous when using (laminated) films on a packaging line at a packaging speed of 50 to 80 bags / minute.
[0424] Table 10: Printed film performance (27μm PE film).
[0425]
[0426]
[0427] Referring to Table 10, compared to the comparative CE2 printed film, the IE2 and IE3 printed films achieved higher tensile modulus (1% secant modulus) and higher tensile strength. The film properties obtained using the described formulations show that the IE2 and IE3 printed films have secant modulus in the range of 620 MPa to 660 MPa at 1% (MD), indicating high stiffness and providing excellent bulk to meet the requirements of high-speed printing operations and improve the overall stiffness of the laminate, thereby facilitating laminate operations at higher packaging speeds.
[0428] The improved barrier properties (WVTR and OTR) and good optical properties (haze and gloss) of IE2 and IE3 printed films are described.
[0429] Compared to the CE2 sample, the inner layers of IE2 and IE3 exhibit an increased sealing initiation temperature at 5N.
[0430] Figure 3 This indicates that the polyethylene substrate of the present invention has improved heat resistance (the inner layers of IE2 and IE3 show increased seal initiation temperatures at 5 N compared to the CE2 sample, and within the range of 110°C to 120°C), which contributes to the production of higher δSIT (ΔSIT). δSIT (ΔSIT) is calculated as the difference between the seal initiation temperature (SIT) of the printed film layer G and the seal initiation temperature (SIT) of the sealing film layer C. Therefore, IE2 and IE3 films can withstand the high temperatures of the top vertical sealing strip of the FFS packaging machine and can also produce high δSIT (between the outer and inner lamination surfaces).
Claims
1. A polyethylene laminate comprising an inner surface and an outer surface, wherein the laminate comprises: a) A printed film comprising an outer layer E, a core layer F, and an inner layer G, wherein the inner layer G forms the outer surface of a laminated film, and wherein the inner layer G is composed of an inner layer G composition comprising component AG, wherein component AG is an ethylene copolymer having a content of 920 kg / m³. 3 Up to 935 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, from 0.5 g / 10 min to 2.0 g / 10 min, wherein, The ethylene copolymer is a multimodal copolymer of ethylene and at least two different C4 to C12 α-olefin monomers; and b) A sealing film comprising an outer layer A, a core layer B and an inner layer C, wherein the inner layer C forms the inner surface of a laminated film, and wherein the inner layer C is composed of an inner layer C composition comprising at least one ethylene polymer. Wherein, the outer layer A of the sealing film is laminated onto the outer layer E of the printed film, and The sealing initiation temperature (SIT) of the outer surface of the laminate at 5N is at least 10°C higher than the sealing initiation temperature of the inner surface of the laminate at 5N, and the sealing initiation temperature is determined according to ASTM F2029 and ASTM F88.
2. The polyethylene laminate according to claim 1, wherein, The inner layer C composition comprises component AC, which is a linear low-density ethylene polymer with a density of 915 kg / m³. 3 Up to 925 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, from 0.5 g / 10 min to 2.0 g / 10 min.
3. The polyethylene laminate according to claim 2, wherein, Based on the total weight of the inner layer G composition, the inner layer G composition of the printed film contains 50 wt.% to 75 wt.% of component AG; and / or the inner layer C composition of the sealing film contains component AC, which is a linear low-density ethylene polymer with a density of 915 kg / m³. 3 Up to 925 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, from 0.5 g / 10 min to 2.0 g / 10 min, wherein the density of component AC is lower than that of component AG.
4. The polyethylene laminate according to claim 3, wherein, The inner layer G composition of the printed film further comprises: component BG1, which is a linear low-density ethylene polymer with a density of 915 kg / m³. 3 Up to 930 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, from 0.05 g / 10 min to 1.0 g / 10 min; and / or component BG2, which is a high-density ethylene polymer with a melt flow rate of 950 kg / m³. 3 Up to 970 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, are 0.2 g / 10 min to 2.0 g / 10 min.
5. The polyethylene laminate according to claim 4, wherein, Any or all of the components AC, AG, and BG2 are bimodal ethylene copolymers.
6. The polyethylene laminate of claim 5, wherein any one or both of components AC and AG are copolymers of ethylene with at least two different C4 to C12 α-olefin monomers.
7. The polyethylene laminate according to any one of claims 3 to 6, wherein, The inner layer C composition of the sealing membrane also includes component BC, which is low-density polyethylene with a density of 918 kg / m³. 3 Up to 928 kg / m 3 The density and melt flow rate MFR2, determined according to ISO 1133, are 1.5 g / 10 min to 2.5 g / 10 min.
8. The polyethylene laminate according to any one of claims 1 to 6, wherein, The core layer F of the printed film is composed of a core layer F composition containing component AF, which is a high-density ethylene polymer with a density of 950 kg / m³. 3 Up to 970 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, are 0.2 g / 10 min to 2.0 g / 10 min.
9. The polyethylene laminate according to claim 8, wherein, The core layer F composition of the printed film also includes component BF, which is an ethylene copolymer with a content of 920 kg / m³. 3 Up to 935 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, from 0.5 g / 10 min to 2.0 g / 10 min.
10. The polyethylene laminate according to any one of claims 1 to 6, wherein, The core layer B of the sealing film is composed of a core layer B composition comprising: component AB, wherein component AB is medium-density polyethylene with a density of 925 kg / m³. 3 Up to 945 kg / m 3 The density and melt flow rate MFR2, determined according to ISO 1133, ranging from 0.05 g / 10 min to 0.50 g / 10 min; and / or component BB, which is a linear low-density ethylene polymer with a density of 915 kg / m³. 3 Up to 925 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, from 0.5 g / 10 min to 2.0 g / 10 min.
11. The polyethylene laminate according to any one of claims 1 to 6, wherein, The outer layer A of the sealing membrane is composed of a composition comprising: component AA, which is a linear low-density ethylene polymer having a density of 915 kg / m³. 3 Up to 930 kg / m 3 The density and melt flow rate MFR2, determined according to ISO 1133, ranging from 0.05 g / 10 min to 1.0 g / 10 min; and / or component BA, which is a linear low-density ethylene polymer with a density of 915 kg / m³. 3 Up to 925 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, from 0.5 g / 10 min to 2.0 g / 10 min.
12. The polyethylene laminate according to any one of claims 1 to 6, wherein, Meets one or more of the following criteria: a) The laminated film and / or sealing film and / or printed film have a haze value of less than 12% as determined by ASTM D1003; b) According to ISO 2813, the laminated film and / or sealing film and / or printed film have a gloss value of at least 80, which is determined at 60° at the corresponding inner layer C / G or outer layer A / E. c) The 1% secant tensile modulus of the sealing film in the machine direction is 280 MPa to 500 MPa, and / or 500 MPa to 1000 MPa for printed films, and / or 400 MPa to 800 MPa for laminated films, as determined by ASTM D882. d) The laminated film, measured according to ASTM F-1249 at 37.8°C and 90% RH, has a strength of not more than 5 g / m³. 2 / d water vapor transmission rate (WVTR); and e) The laminated film, measured according to ISO 15105-2 at 23°C and 0% RH, has a thickness of not more than 2000 cm⁻¹. 3 / m 2 Oxygen permeability (OTR) per day.
13. The polyethylene laminate according to any one of claims 1 to 6, wherein, The printed film has a thickness of 15 µm to 40 µm, and the sealing film has a thickness of 35 µm to 120 µm, wherein each of the printed film and the sealing film comprises up to seven layers and is produced by a blown film or casting process.
14. The polyethylene laminate according to claim 13, wherein, Each of the printed film and the sealing film is a non-directional film.
15. The polyethylene laminate according to claim 13, wherein, The laminated film comprises an adhesive layer between the outer layer A of the sealing film and the outer layer E of the printed film.
16. The polyethylene laminate according to any one of claims 1 to 6, wherein, The sealing membrane comprises an outer layer A, a core layer B, and an inner layer C. The inner layer C is composed of an inner layer C composition comprising the following: a) Component AC, which is a linear low-density ethylene polymer with a density of 915 kg / m³. 3 Up to 925 kg / m 3 The density and melt flow rate MFR2, determined according to ISO 1133, from 0.5 g / 10 min to 2.0 g / 10 min, wherein the linear low-density ethylene polymer is a multimodal copolymer of ethylene and at least two different C4 to C12 α-olefin monomers; and b) Component BC, which is low-density polyethylene with a density of 918 kg / m³. 3 Up to 928 kg / m 3 The density and melt flow rate MFR2, determined according to ISO 1133, ranging from 1.5 g / 10 min to 2.5 g / 10 min; and It meets at least one of the following criteria: c) The core layer B is composed of a core layer B composition containing component AB, wherein component AB is medium-density polyethylene with a density of 925 kg / m³. 3 Up to 945 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, from 0.05 g / 10 min to 0.50 g / 10 min; and d) The outer layer A is composed of an outer layer A composition containing component AA, which is a linear low-density ethylene polymer with a density of 915 kg / m³. 3 Up to 930 kg / m 3 The density and melt flow rate MFR2, measured according to ISO 1133, are 0.05 g / 10 min to 1.0 g / 10 min.
17. An article comprising a polyethylene laminate according to any one of claims 1 to 16.
18. The use of the polyethylene laminate according to any one of claims 1 to 16 in the packaging of articles.
Citation Information
Patent Citations
COMPOSITION AND METHOD FOR REGULATING PLANT GROWTH
BG20066A3
Breathable films
WO2004000933A1
Polyethylene composition for a film layer
WO2016083208A1
Compatible heterogeneous polymer blends
WO2017021389A1
Coextruded structures for collation shrink films
WO2017055174A1